Electrode composition

Hybrid electrode particles with a metal and oxide phase improve electrode stability and performance in solid oxide electrochemical cells, addressing degradation issues and reducing costs, enabling efficient production of hydrogen and synthesis gas.

CN119213587APending Publication Date: 2024-12-27COMMONWEALTH SCI & IND RES ORG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380032727.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-06
Filing Date
2023-04-06
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing solid oxide electrochemical cells face challenges such as high capital costs, susceptibility to degradation, and the need for external reducing gases to maintain electrode stability, which hinder their economic viability and efficiency.

Method used

Development of hybrid electrode particles comprising a metal phase and an oxide phase, with ion- or mixed-ion-conducting oxide particles on the surface of the metal particles, prepared using a sol-gel method, which can be used as both positive and negative electrodes in solid oxide electrochemical cells.

Benefits of technology

The hybrid electrode particles enhance electrode performance and stability, reducing polarization losses and enabling faster manufacturing, making the technology scalable for industrial applications in producing hydrogen, CO, and synthesis gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005072443060000301
    Figure BDA0005072443060000301
  • Figure BDA0005072443060000521
    Figure BDA0005072443060000521
  • Figure BDA0005072443060000531
    Figure BDA0005072443060000531
Patent Text Reader

Abstract

The present disclosure relates to electrode compositions, in particular to electrode compositions comprising hybrid electrode particles that can be used in solid oxide electrochemical cells. The present disclosure also relates to methods for preparing hybrid electrode particles. The present disclosure also relates to an electrode comprising the electrode composition, comprising a sintered electrode, and to a solid oxide electrochemical cell comprising the electrode composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrode composition, in particular to an electrode composition comprising hybrid electrode particles that can be used in a solid oxide electrochemical cell. The present disclosure also relates to a method for preparing hybrid electrode particles. The present disclosure also relates to an electrode (including a sintered electrode) comprising the electrode composition, and to a solid oxide electrochemical cell comprising the electrode composition. Background Art

[0002] Electrochemical cells, including solid oxide electrolysis cells (SOECs) and solid oxide fuel cells (SOFCs), offer many advantages over existing energy system technologies, such as natural gas reforming and coal-fired power plants for hydrogen production. For example, solid oxide electrolysis cells (SOECs) have great potential to provide a practical way to produce high purity hydrogen, CO or synthesis gas on demand by using water and recycled waste CO2 from industrial processes. In particular, hydrogen, CO and / or synthesis gas are important raw materials for the production of many chemicals required by the pharmaceutical, food and plastics industries. In addition, hydrogen can be used directly in the energy sector or for further production of various value-added fuels as described above, such as green ammonia, methanol, dimethyl ether, etc.

[0003] Although pre-commercial demonstrations are promising, there are still some key technical challenges that need to be addressed to make this technology economically viable. These challenges include reducing capital costs using low-cost materials and cell designs, as well as improving electrode performance and service life, including identifying new and improved electrode materials, which are key drivers of electrochemical performance. Other current problems with current electrodes (e.g., conventional nickel-YSZ cathodes) include susceptibility to degradation in fuel environments or oxidizing environments, high cell manufacturing and operating temperatures. In addition, an external reducing gas is required in the feed stream to maintain the current electrode in a reduced state, which adds cost and complexity.

[0004]

[0006] Therefore, there is a need for alternative or improved electrode compositions for solid oxide electrochemical cells, and methods for preparing electrode compositions for solid oxide electrochemical cells that are scalable for industrial applications.

[0005] It should be understood that reference to any prior art publication herein does not constitute an admission that any of those documents forms part of the common general knowledge in the art, in Australia or any other country. Summary of the invention

[0006] The present disclosure provides specific electrode compositions that can be expanded for industrial applications and provide control, flexibility and consistency in the manufacture of electrodes (including electrodes for solid oxide electrochemical cells (e.g., solid oxide electrolysis cells (SOECs) and solid oxide fuel cells (SOFCs)) for the production of various products such as fuel gas (using SOECs) and electricity (using SOFCs). Advantageously, the electrode composition can be used as a positive electrode and / or a negative electrode. In one example, the electrode composition described herein can be used to prepare a symmetrical solid oxide electrochemical cell. The present disclosure also relates to various electrodes, solid oxide electrolysis cells, solid oxide fuel cell cells, processes, systems, generators, sensors and / or reactors that can utilize the electrode composition.

[0007] In one aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises at least one metal phase and an oxide phase, wherein the metal phase comprises a plurality of metal particles, and the oxide phase comprises a plurality of ion- or mixed-ion-conducting oxide particles on the surface of the metal particles, and wherein each hybrid electrode particle comprises a plurality of ion- or mixed-ion-conducting oxide particles on the surface of the metal particles, wherein the particle size (in nm) of the ion- or mixed-ion-conducting oxide particles on the surface of the metal particles is between about 1 and 200.

[0008] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises at least one metal phase and an oxide phase, wherein the metal phase comprises a plurality of metal particles, and the oxide phase comprises a plurality of ion or mixed ion conducting oxide particles on the surface of the metal particles, wherein the plurality of ion or mixed ion conducting oxide particles decorate the surface of the metal particles, and wherein the particle size (in nm) of the ion or mixed ion conducting oxide particles on the surface of the metal particles is between about 1 and 100.

[0009] In some embodiments, the metal phase comprises at least one metal particle selected from the group consisting of silver (Ag), iron (Fe), nickel (Ni), and cobalt (Co). In other embodiments, the metal phase comprises a combination of silver (Ag) particles and one or more of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu), and titanium (Ti). In some embodiments, the oxide phase comprises ion or mixed ion conducting oxide particles selected from the group consisting of metal (e.g., Gd, Sm, Pr, Ni) doped ceria, metal (e.g., Cu) doped ferrites, doped lanthanum strontium ferrites (e.g., LSCF, LSTF), and lanthanum strontium chromium manganese (LSCM).

[0010] In another aspect, an electrode composition is provided that includes a plurality of hybrid electrode particles, wherein each hybrid electrode particle includes a silver particle having a surface including one or more metal-doped ceria particles.

[0011] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped ceria particles, wherein the one or more metal-doped ceria particles are decorated on the surface of the silver particle.

[0012] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped ceria particles, wherein the silver particle has a particle size greater than a particle size of the metal-doped ceria particles.

[0013] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped ceria particles, wherein the one or more metal-doped ceria particles are decorated on the surface of the silver particle, and the particle size of the silver particle is larger than the particle size of the metal-doped ceria particles.

[0014] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more ionic or mixed ionic conductive oxide particles, wherein the one or more ionic or mixed ionic conductive oxide particles are decorated on the surface of the silver particle; and the particle size (in nm) of the ionic or mixed ionic conductive oxide particles on the surface of the silver particle is between about 1 and 100.

[0015] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped cerium oxide particles, wherein the particle size (in μm) of the hybrid electrode particle is between about 0.05 and 5, and the particle size (in nm) of the metal-doped cerium oxide particles on the surface of the silver particle is between about 1 and 200.

[0016] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped cerium oxide particles, wherein the particle size (in μm) of the hybrid electrode particle is between about 0.05 and 5, and the particle size (in nm) of the metal-doped cerium oxide particles on the surface of the silver particle is between about 1 and 100.

[0017] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped cerium oxide particles, wherein the one or more metal-doped cerium oxide particles are decorated on the surface of the silver particle, and wherein the particle size (in μm) of the hybrid electrode particle is between about 0.05 and 5, and the particle size (in nm) of the metal-doped cerium oxide particles on the surface of the silver particle is between about 1 and 100.

[0018] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped cerium oxide particles, wherein the particle size of the silver particle is larger than the particle size of the metal-doped cerium oxide particles, and wherein the particle size (in μm) of the hybrid electrode particle is between about 0.05 and 5, and the particle size (in nm) of the metal-doped cerium oxide particles on the surface of the silver particle is between about 1 and 100.

[0019] In another aspect, an electrode composition is provided, comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped cerium oxide particles, wherein the one or more metal-doped cerium oxide particles are decorated on the surface of the silver particle, and the particle size of the silver particle is larger than the particle size of the metal-doped cerium oxide particles, and wherein the particle size (in μm) of the hybrid electrode particle is between about 0.05 and 5, and the particle size (in nm) of the metal-doped cerium oxide particles on the surface of the silver particle is between about 1 and 100.

[0020] In another aspect, there is provided an improved sol-gel method for preparing hybrid electrode particles, wherein each hybrid electrode particle comprises at least one metal phase and one oxide phase, wherein the metal phase comprises at least one metal particle, and the oxide phase comprises a plurality of ion or mixed ion conducting oxide particles on the surface of the metal particle, wherein the plurality of ion or mixed ion conducting oxide particles decorate the surface of the metal particle, wherein the particle size (in nm) of the ion or mixed ion conducting oxide particles on the surface of the metal particle is between about 1 and 100, wherein the method comprises:

[0021] a) preparing a gel from an aqueous solution comprising a metal species, an ion or mixed ion conducting oxide species, a plasticizer and a chelating agent; and

[0022] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0023] In another aspect, there is provided an improved sol-gel method for preparing hybrid electrode particles, wherein the method comprises:

[0024] a) preparing a gel from an aqueous solution comprising a silver metal species, a cerium metal species, a metal dopant species, a plasticizer, and a chelating agent; and

[0025] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0026] In another aspect, there is provided an improved sol-gel method for preparing hybrid electrode particles, wherein the method comprises:

[0027] a) preparing a gel from an aqueous solution comprising a bimetallic metal species, a cerium metal species, a metal dopant species, a plasticizer, and a chelating agent; and

[0028] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0029] In another aspect, there is provided an improved sol-gel method for preparing hybrid electrode particles, wherein the method comprises:

[0030] a) preparing a gel from an aqueous solution comprising a bimetallic metal species, a metal-doped ferrite, a plasticizer and a chelating agent; and

[0031] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0032] In another aspect, an electrode is provided, comprising the electrode composition described herein or a sintered electrode material thereof.

[0033] In another aspect, a solid oxide electrochemical cell is provided, comprising a cathode, a solid oxide electrolyte, and an anode, wherein the cathode and / or the anode comprises the electrode composition described herein or a sintered electrode material thereof.

[0034] In another aspect, there is provided a use of the electrode composition described herein in the preparation of an electrode or electrode material for a solid oxide electrochemical cell.

[0035] In another aspect, a method of making a solid oxide electrochemical cell is provided, the method comprising:

[0036] a) preparing one or more solid oxide electrolyte layers;

[0037] b) applying an electrode composition to one or both sides of the solid oxide electrolyte layer to form a solid oxide electrochemical cell assembly, wherein the electrode composition applied to at least one side of the solid oxide electrolyte layer comprises an electrode composition described herein; and

[0038] c) sintering the electrode composition applied to the solid oxide electrochemical cell assembly to form an electrode or electrode material.

[0039] It should be understood that any one or more of the embodiments and examples described herein for electrode compositions or their sintered electrode materials may also be applicable to electrodes, solid oxide electrolysis cells, solid oxide fuel cell cells, processes, systems, generators, sensors and / or reactors described herein. Unless otherwise expressly stated, any embodiment herein shall be deemed applicable to any other embodiment after making necessary modifications. It should also be understood that other aspects, embodiments and examples of electrode compositions or their sintered electrode materials, electrodes, solid oxide electrolysis cells, solid oxide fuel cell cells, processes, systems, generators, sensors and / or reactors are described herein.

[0040] It is also understood that some features of the electrode composition or its sintered electrode material, electrode, solid oxide electrolysis cell unit, solid oxide fuel cell unit, process, system, generator, sensor and / or reactor identified in some aspects, embodiments or examples as described herein may not be required in all aspects, embodiments or examples as described herein, and this specification will be read in this context. It is also understood that in various aspects, embodiments or examples, the order of method or process steps may not be required and may vary. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Preferred embodiments of the present disclosure will now be further described and illustrated as follows, by way of example only, with reference to the accompanying drawings, in which:

[0042] Figure 1 : Schematic representation of a hybrid electrode particle comprising a metal particle decorated with one or more mixed ion-conducting phases / metal oxide phases.

[0043] Figure 2 : Schematic diagram of an electrode composition comprising a plurality of hybrid electrode particles provided in a layer on an electrolyte, provided for use as an anode in a solid oxide electrolysis mode.

[0044] Figure 3 : Schematic diagram of an electrode composition comprising a plurality of hybrid electrode particles provided in a layer on an electrolyte, provided for use as a cathode in a solid oxide electrolysis mode.

[0045] Figure 4 : Scanning electron microscopy image of a sintered electrode material comprising a silver metal phase and one or more metal-doped ceria particles or discrete portions dispersed within the silver metal phase.

[0046] Figure 5 : Energy dispersive spectroscopy (EDS) layered image of a sintered electrode material comprising a silver metal phase and one or more metal-doped ceria particles or discrete portions dispersed within the silver metal phase.

[0047] Figure 6 : Current-voltage curves for a tubular solid oxide electrolysis cell using the following as electrodes for steam electrolysis: a sintered material comprising a silver metal phase and one or more metal-doped ceria particles or discrete portions dispersed within the silver metal phase; a Ni-YSZ composite; or a mixed CGO-AG.

[0048] Figure 7: Current-voltage curves for steam electrolysis using a tubular symmetrical solid oxide electrolysis cell unit: a sintered electrode material comprising a silver metal phase and one or more mixed ionic and electronic conductor ferrite phases (LSCF) or discrete portions dispersed within the silver metal phase; mixed Ag-LSCF.

[0049] Figure 8 : Current-voltage curves for steam electrolysis using a tubular asymmetric solid oxide electrolysis cell unit: a sintered electrode material comprising one or more metal phases and one or more metal-doped ceria particles or discrete portions dispersed within the metal phase; mixed Fe-Ag-GDC.

[0050] Fig. 9 : Electrode polarization resistance of a tubular symmetrical solid oxide electrolysis cell unit for steam electrolysis using: a sintered electrode material comprising a silver metal phase and one or more metal-doped ceria particles or discrete portions dispersed within the silver metal phase; mixed Ag-GDC.

[0051] Fig.10 : Short term performance of steam electrolysis using a tubular solid oxide electrolysis cell using as electrodes: a sintered material comprising a silver metal phase and one or more metal-doped ceria particles or discrete portions dispersed within the silver metal phase.

[0052] Fig.11 : Schematic diagram of a tube battery cell setup using one or more electrodes comprising a sintered hybrid electrode material according to some embodiments or examples described herein. DETAILED DESCRIPTION

[0053] The present disclosure describes the following various non-limiting embodiments, which relate to research conducted in order to identify electrode compositions. Other non-limiting embodiments of electrode compositions, electrodes, solid oxide electrochemical cells, solid oxide fuel cell cells, processes, systems, generators, sensors and / or reactors are also described. Solid oxide fuel cell cells (SOFC) can convert chemical energy in fuels (such as hydrogen, hydrocarbon fuels, ammonia, methane, etc.) into electricity with high efficiency, and solid oxide electrolysis cells (SOEC) can be stored in the form of chemical fuels (such as CO, H2, other hydrocarbon fuels such as syngas) by the electrolysis of molecules such as H2O, CO2 and N2 from "excess" renewable energy. In other words, solid oxide electrolysis cells (SOEC) can be used to store excess energy in the form of fuel when renewable sources are higher than demand. The stored fuel can then be used for combined heat and power applications by solid oxide fuel cell cells (SOFC). This means that a reversible solid oxide cell (RSOC) may be desired, and the RSOC can produce synthetic fuels from electricity or can produce electricity from fuel when reversed.

[0054] The electrode composition described herein includes a plurality of hybrid electrode particles, which are further described below according to various non-limiting embodiments and examples. It was surprisingly found that the electrode composition described herein provides one or more advantages, including the synthesis of various products, such as fuel gas. At least according to some embodiments or examples described herein, the electrode composition can be advantageously used as both the positive electrode and the negative electrode of a solid oxide electrochemical cell. It has been found that such a symmetrical solid oxide electrochemical cell can make the manufacturing time faster and is therefore a scalable and efficient industrial method for preparing a solid oxide electrochemical cell. Other applications and advantages associated with the electrode composition are also described herein.

[0055] the term

[0056] In the following description, reference is made to the accompanying drawings, which form a part of the detailed description and which show several embodiments by way of illustration. It should be understood that other embodiments may be utilized and structural changes may be made without departing from the scope of the present disclosure.

[0057] With respect to the definitions provided herein, unless otherwise stated or implied from the context, the defined terms and phrases include the meanings provided. Unless otherwise expressly stated or apparent from the context, the following terms and phrases do not exclude the meanings of the terms or phrases as acquired by those skilled in the relevant art. These definitions are provided to help describe specific embodiments, and these definitions are not intended to limit the claimed invention, as the scope of the invention is limited only by the claims. In addition, unless the context otherwise requires, singular terms shall include the plural and plural terms shall include the singular.

[0058] All publications discussed and / or cited herein are incorporated herein in their entirety.

[0059] Any discussion of documents, acts, materials, devices, articles or the like that has been included in this specification is solely for the purpose of providing context for the present disclosure. It is not to be taken as an admission that any or all of these matters form part of the prior art base or are common general knowledge in the field relevant to the present disclosure as they existed before the priority date of each claim of this application.

[0060] Throughout this disclosure, references to individual steps, compositions of matter, groups of steps, or groups of compositions of matter shall be deemed to encompass one and multiple (i.e., one or more) of these steps, compositions of matter, groups of steps, or groups of compositions of matter, unless otherwise specifically stated or the context requires otherwise. Thus, as used herein, the singular forms "a," "an," and "the" include plural aspects unless the context clearly dictates otherwise. For example, reference to "a" includes a single as well as two or more; reference to "a" includes a single as well as two or more; reference to "the" includes a single as well as two or more, etc.

[0061] Those skilled in the art will appreciate that, in addition to the disclosure specifically described, changes and modifications may be made to the disclosure herein. It should be understood that the disclosure encompasses all such changes and modifications. The disclosure also encompasses all examples, steps, features, methods, compositions, coatings, processes, and coated substrates that are individually or collectively mentioned or indicated in this specification, as well as any and all combinations of any two or more of the steps or features.

[0062] The term "and / or" (eg, "X and / or Y") should be understood to mean "X and Y" or "X or Y," and should be considered to provide clear support for both or either meanings.

[0063] Unless otherwise indicated, the terms "first," "second," and the like are used herein merely as labels and are not intended to impose ordinal, positional, or hierarchical requirements on the items to which these terms refer. Furthermore, reference to a "second" item does not require or preclude the presence of a lower-numbered item (e.g., a "first" item) and / or a higher-numbered item (e.g., a "third" item).

[0064] As used herein, when used with a list of items, the phrase "at least one of" means that different combinations of one or more of the listed items may be used, and only one item of each item in the list may be required. An item may be a specific object, thing, or category. In other words, "at least one of" means that any combination or number of items in the list may be used, but not all items in the list are required. For example, "at least one of item A, item B, and item C" may mean item A; item A and item B; item B; item A, item B, and item C; or item B and item C. In some cases, "at least one of item A, item B, and item C" may mean, for example, but not limited to, two of item A, one of item B, and ten of item C; four of item B and seven of item C; or some other suitable combination.

[0065] As used herein, unless stated to the contrary, the term "about" generally means + / - 10%, eg, + / - 5%, of a specified value.

[0066] It should be understood that, for the sake of clarity, certain features described herein in the context of separate embodiments may also be provided in a single embodiment in combination. Conversely, for the sake of brevity, various features described in the context of a single embodiment may also be provided individually or in any sub-combination.

[0067] Throughout this specification, various aspects and compositions of the present invention may be presented in a range format. The range format is included for convenience and should not be interpreted as a fixed limitation on the scope of the present invention. Therefore, unless otherwise indicated, the description of the range should be deemed to have specifically disclosed all possible sub-ranges and individual numerical values ​​within the range. For example, unless an integer is required or the context implies an integer, the description of a range such as 1 to 5 should be deemed to have specifically disclosed sub-ranges, such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 5, 3 to 5, etc.; and individual and partial numbers within the stated range, for example, 1, 2, 3, 4, 5, 5.5 and 6. This applies regardless of the breadth of the disclosed range. When specific values ​​are required, these values ​​will be indicated in the specification.

[0068] Throughout this specification, the word "comprise" or variations such as "comprises" or "comprising" will be understood to imply the inclusion of stated elements, integers or steps, or groups of elements, integers or steps, but not the exclusion of any other elements, integers or steps, or groups of elements, integers or steps.

[0069] Reference to "substantially free" generally means that the compound or component is not present in the composition, except for any trace amounts or impurities that may be present, for example, this may be an amount of less than about 1%, 0.1%, 0.01%, 0.001% or 0.0001% by weight of the total composition.

[0070] "Weight %" may be abbreviated herein as "wt %".

[0071] Electrode composition

[0072] The present disclosure relates to providing improvements in electrode compositions, including improved stability and performance. The present disclosure covers various research and development related to identifying electrode compositions for preparing electrodes, including electrode compositions for solid oxide electrochemical cells (e.g., solid oxide electrolysis cells (SOECs) and solid oxide fuel cells (SOFCs)). One or more advantages of the present disclosure according to at least some embodiments or examples as described herein is that the electrode composition can be used as a positive electrode and / or a negative electrode. In one example, the electrode composition can be used to prepare a symmetrical solid oxide cell, such as a symmetrical SOEC and a symmetrical SOFC.

[0073] The SOEC described herein can be advantageously used to produce fuel gases, such as (1) hydrogen produced by steam electrolysis, (2) carbon monoxide produced by carbon dioxide electrolysis, (3) synthetic gas produced by electrolysis of a mixture of steam and CO2, also known as "syngas", (4) ammonia production by electrolysis of a mixture of steam and nitrogen, and (5) synthetic methane production by electrolysis of a mixture of steam and CO2. The produced fuel gases can be used in various chemical processes or energy production. The SOEC described herein can also be integrated with downstream fuel and chemical production processes to achieve renewable energy storage and export in the form of value-added chemicals and fuels. The SOEC can also use high temperatures (e.g., >600°C) to electrolyze steam / CO2 with high efficiency with the help of thermodynamically favorable steam / CO2 splitting, which can achieve large-scale hydrogen / CO / syngas / ammonia / methane production. One or more advantages of the present disclosure according to at least some embodiments or examples as described herein are that, with the manufacture of commercial-scale SOECs, the technology is increasingly seen as a means of producing sustainable fuels using renewable energy.

[0074] It has been found that electrode compositions comprising a mixture of two or more phases can provide many reaction sites at the interface (i.e., phase boundary) between the two phases in and on the surface of the catalyst composition. Unexpectedly, the resulting microstructure of the electrode composition can provide one or more advantages according to at least some embodiments or examples described herein, including improving the catalytic performance of SOEC. Other advantages provided by the electrode composition are also described herein.

[0075] The electrode composition may include a plurality of hybrid particles. The hybrid electrode particles include at least one metal phase and a metal oxide phase. In an embodiment, the metal phase may include a plurality of metal particles, and the oxide phase includes a plurality of ionic or mixed ionic conductive oxide particles on the surface of the metal particles. Each hybrid electrode particle may include one or more metal particles and one or more ionic or mixed ionic conductive oxide particles. The oxide particles may be doped with one or more additional metals. The metal particles have a surface that may include one or more oxide particles. Each hybrid electrode particle may include a metal particle having a surface that includes one or more ionic or mixed ionic conductive oxide particles. It should be understood that one or more ionic or mixed ionic conductive oxide particles or a plurality of ionic or mixed ionic conductive oxide particles are decorated on the surface of the metal particles. In other words, one or more advantages according to at least some embodiments or examples as described herein can be provided by decorating a plurality of ionic or mixed ionic conductive oxide particles on the surface of the metal particles, because the spacing between the ionic or mixed ionic conductive oxide particles allows free space on the metal particles to form a connected network of metal particles to achieve favorable electronic conductivity and reduce polarization losses in the resulting electrode structure.

[0076] The metal phase may include at least one metal particle selected from silver (Ag), iron (Fe), nickel (Ni) and cobalt (Co). In some embodiments, the metal phase may include a combination of silver (Ag) particles and one or more of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu) and titanium (Ti). In one example, the metal phase may include a combination of silver (Ag) particles and iron (Fe) particles. In other examples, the metal phase may include silver (Ag) particles. The oxide phase may include ionic or mixed ionic conductive oxide particles selected from metal (e.g., Gd, Sm, Pr, Ni) doped cerium oxide, metal (e.g., Cu, Ti, Co) doped ferrite and lanthanum strontium chromium manganese (LSCM). The hybrid electrode particles may include silver particles and one or more ionic or mixed ionic conductive oxide particles. The silver particles have a surface that may include one or more metal oxide particles. The hybrid electrode particles may include one silver particle and one or more cerium oxide particles. The cerium oxide particles may be doped with one or more metals. The silver particles have a surface that may include one or more metal-doped cerium oxide particles. In one embodiment, an electrode composition including a plurality of hybrid electrode particles is provided.

[0077] Hybrid electrode particles

[0078] In some embodiments, the electrode composition includes a plurality of hybrid electrode particles. As used herein, the term "hybrid electrode particle" refers to a single particle including at least two phases, for example, at least one metal phase (eg, silver) and at least one metal oxide phase (eg, ceria).

[0079] In one embodiment, the hybrid electrode particles may be in any form, for example, may be in the form of flakes, fibers, agglomerates, microparticles, powders, balls, crushed materials, and the like, and combinations thereof. The hybrid electrode particles may have any desired shape, including but not limited to cubic, rod-shaped, polyhedral, spherical or hemispherical, circular or semicircular, angular, irregular, and the like. In one embodiment, the aspect ratio (i.e., the ratio of length to width, wherein the length and width are measured perpendicular to each other, and the length refers to the longest linear dimension) of the hybrid electrode particles is 1.0 to 10.0, 1.0 to 5.0, or 1.0 to 2.0. In one embodiment, the aspect ratio of the hybrid electrode particles may be about 1.0 to 2.0, for example, about 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2.0.

[0080] In some embodiments, the particle size (in μm) of the hybrid electrode particles may be at least about 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.5, 0.7, 1, 1.5, 2, 2.5, 3, 3.5, 4, or 5. In some embodiments, the particle size (in μm) of the hybrid electrode particles may be less than about 5, 4, 3.5, 3, 2.5, 2, 1.5, 1, 0.7, 0.5, 0.2, 0.1, 0.09, 0.08, 0.07, 0.06, or 0.05. Combinations of any two or more of these higher particle sizes and / or lower particle sizes are also possible, for example, the particle size (in μm) of the hybrid electrode particles may be between about 0.05 and 5, 0.06 and 4, or 0.07 and 3.5. The particle size is considered to be the longest cross-sectional diameter across the hybrid electrode particles. For non-spherical hybrid electrode particles, the particle size is taken as the distance corresponding to the longest cross-sectional dimension across the particle.

[0081] 0% to 100% of the hybrid electrode particles have a particle size distribution in the range of 0.05-5 μm, and vice versa. For example, 80% of the particle size will be in the range of 0.05-3 μm, and 20% of the particle size will be in the range of 3-5 μm. Other percentages and combinations of higher and / or lower particle sizes are also possible.

[0082] The particle size and / or particle size distribution can be measured by any standard method, such as laser diffraction, electron microscopy (e.g., TEM or SEM), X-ray diffraction (e.g., Scherrer equation), or dynamic light scattering. In one embodiment, the particle size and / or particle size distribution can be measured using laser diffraction according to industry standard ISO 13320:2020.

[0083] Metal particles

[0084] The metal particles of the hybrid electrode particles may include at least one metal particle selected from silver (Ag), iron (Fe), nickel (Ni) and cobalt (Co). In some embodiments, the metal particles may include a combination of silver (Ag) particles and one or more of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu) and titanium (Ti). In other embodiments, the metal particles of the hybrid electrode particles may include a combination of silver (Ag) particles and iron (Fe) particles. It should be understood that the hybrid electrode particles include silver (Ag) particles with high conductivity, which can help electrons transfer across the hybrid electrode particles and thus transfer throughout the electrode composition.

[0085] In one embodiment, the metal particles of each hybrid electrode particle can be in any form, for example, it can take the form of flakes, fibers, agglomerates, particles, powders, balls, crushed materials, etc. and combinations thereof. The metal particles of each hybrid electrode particle can have any desired shape, including but not limited to cubic, rod-shaped, polyhedral, spherical or hemispherical, circular or semicircular, angular, irregular, etc. In one embodiment, the aspect ratio (i.e., the ratio of length to width, where the length and width are measured perpendicular to each other, and the length refers to the longest linear dimension) of the metal particles of each hybrid electrode particle can be 1.0 to 10.0, 1.0 to 5.0 or 1.0 to 2.0. In one embodiment, the aspect ratio of the metal particles of each hybrid electrode particle can be about 1.0 to 2.0, for example, about 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0.

[0086] In some embodiments, the particle size (in μm) of the metal particles of each hybrid electrode particle is at least about 0.01, 0.05, 0.1, 0.2, 0.5, 0.7, 1, 1.5, 2, 2.5, 3, 3.5, 4, or 5. In some embodiments, the particle size (in μm) of the metal particles of each hybrid electrode particle is less than about 5, 4, 3.5, 3, 2.5, 2, 1.5, 1, 0.7, 0.5, 0.2, 0.1, 0.05, or 0.01. Combinations of any two or more of these higher particle sizes and / or lower particle sizes are also possible. In some embodiments, the particle size (in μm) of the silver particles of each hybrid electrode particle is at least about 0.01, 0.05, 0.1, 0.2, 0.5, 0.7, 1, 1.5, 2, 2.5, 3, 3.5, 4, or 5. In some embodiments, the particle size (in μm) of the silver particles of each hybrid electrode particle is less than about 5, 4, 3.5, 3, 2.5, 2, 1.5, 1, 0.7, 0.5, 0.2, 0.1, 0.05 or 0.01. Combinations of any two or more of these higher particle sizes and / or lower particle sizes are also possible, for example, the particle size (in μm) of the silver particles of each hybrid electrode particle is between about 0.01 to 5, 0.05 to 5, 0.01 to 4 or 0.05 to 4. The particle size is taken as the longest cross-sectional diameter across the metal particle. For non-spherical metal particles, the particle size is taken as the distance corresponding to the longest cross-sectional dimension across the particle. The particle size of the metal particles of each hybrid electrode particle can be measured by electron microscopy (e.g., TEM or SEM) or X-ray diffraction (e.g., Scherrer analysis of one or more diffraction peaks).

[0087] In some embodiments, the total amount of metal particles in the hybrid electrode particles (based on the total weight of the hybrid electrode particles, in % w / w) is at least 10, 15, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75 or 80. In some embodiments, the total amount of metal particles in the hybrid electrode particles (based on the total weight of the hybrid electrode particles, in % w / w) is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15 or 10. Combinations of any two or more of these higher and / or lower amounts are also possible. In some embodiments, the total amount of silver in the hybrid electrode particles (based on the total weight of the hybrid electrode particles, in % w / w) is at least 10, 15, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75 or 80. In some embodiments, the total amount of silver in the hybrid electrode particles (based on the total weight of the hybrid electrode particles, in % w / w) is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15 or 10. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the total amount of silver in the hybrid electrode particles can be between about 40% w / w and 75% w / w. In some embodiments, the total amount of silver in the hybrid electrode particles (based on the total weight of the hybrid electrode particles, in % w / w) is about 10, 15, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75 or 80. The amount of metal and metal-doped cerium dioxide in the hybrid electrode particles can be determined using electron microscopy, including energy dispersive X-ray spectroscopy (EDS).

[0088] Ion or mixed ion conducting oxide particles

[0089] The oxide phase may include ion or mixed ion conducting oxide particles selected from metal (e.g., Gd, Sm, Pr, Ni) doped ceria, metal (e.g., Cu) doped ferrites, doped lanthanum strontium ferrites (e.g., LSCF, LSTF) and doped lanthanum strontium chromate (e.g., LSCM).

[0090] By introducing metal dopants into ceria, one or more oxygen vacancies are generated. The high concentration and high mobility of oxygen ion vacancies produce metal-doped ceria particles with high mixed ion and electronic conductivity. For example, silver particles have a surface that can include one or more metal-doped ceria particles (also known as cerium (IV) oxide (CeO2)).

[0091] In one embodiment, the metal particles (e.g., silver) have a surface including a plurality of ionic or mixed ionic conductive oxide particles. The metal particles can act as a support / scaffold for the plurality of ionic or mixed ionic conductive oxide particles. It should be understood that the hybrid electrode particles are single particles and are not merely a mixture of individual metal particles and ionic or mixed ionic conductive oxide particles. It should be understood that each hybrid electrode particle includes a metal particle and a plurality of ionic or mixed ionic conductive oxide particles provided (i.e., decorated) on the surface of the metal particle. In other words, the plurality of ionic or mixed ionic conductive oxide particles are dispersed, incorporated, or embedded on the surface of the metal particles, rather than being provided as separate particles in the composition. For example, one or more metal-doped ceria particles are decorated on the surface of the silver particles. In other words, one or more advantages according to at least some embodiments or examples as described herein can be provided by decorating a plurality of ionic or mixed ionic conductive oxide particles (e.g., metal-doped ceria particles) on the surface of the metal particles (e.g., silver particles), because the spacing between the ionic or mixed ionic conductive oxide particles allows free space on the metal particles to form a connected network of metal particles to achieve favorable electronic conductivity and reduce polarization losses in the resulting electrode structure. Reference Figure 1 , shows an example of a hybrid electrode particle including a single metal (e.g., silver) particle, wherein one or more ion or mixed ion conducting oxide particles (e.g., metal-doped ceria nanoparticles) are provided on the surface of the metal (e.g., silver) particle, thereby forming a hybrid particle. For example, the particle size of the metal (silver) particle may be larger than the particle size of the ion or mixed ion conducting oxide particle.

[0092] Without wishing to be bound by theory, the connection points at the interface between the metal surface and the ionic or mixed ionic conducting oxide particles provide multiple reactive sites on each hybrid electrode particle. For example, the silver particles and metal-doped ceria particles on each hybrid electrode particle can promote the movement of electrons and / or mobile oxygen species (O 2- ) are transported from or to reactive sites located on the surface of each hybrid electrode particle, respectively, for example, when used as an electrode composition in a SOEC or SOFC. Due to the unique microstructure of the hybrid electrode particles, ion and electron pathways are created to allow electrons and mobile oxygen species (O 2- ) is transferred to and from the reactive sites located on the surface of each hybrid electrode particle. The position of a reactive site is Figure 2 and 3 (enlarged) is provided by way of example for electrode compositions comprising hybrid electrode particles when used as oxygen and fuel electrodes in a solid oxide electrolysis cell (SOEC).

[0093] In some embodiments, at least 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50% of the surface of the metal particles of each hybrid electrode particle may include ionic or mixed ionic conductive oxide particles. In some embodiments, less than 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, or 50% of the surface of the metal particles of each hybrid electrode particle may include ionic or mixed ionic conductive oxide particles. A plurality of ionic or mixed ionic conductive oxide (e.g., metal-doped cerium oxide) particles may be irregularly spaced on the surface of the metal (e.g., silver) particles. It should be understood that the irregular spacing across the surface of the metal particles creates free space on the surface to form a connected network of metal particles, thereby providing one or more advantages according to at least some embodiments or examples as described herein. The amount of ionic or mixed ionic conductive oxide particles present on the surface of the metal particles can be determined using electron microscopy, including energy dispersive X-ray spectroscopy (EDS) in scanning transmission electron microscopy (STEM). An example of this is shown in Figure 5 middle.

[0094] In one embodiment, the ionic or mixed ionic conductive oxide (e.g., metal-doped ceria) particles of each hybrid electrode particle may be in any form, for example, may be in the form of flakes, fibers, agglomerates, microparticles, powders, balls, crushed materials, etc. and combinations thereof. The ionic or mixed ionic conductive oxide (e.g., metal-doped ceria) particles of each hybrid electrode particle may have any desired shape, including but not limited to cubic, rod-shaped, polyhedral, spherical or hemispherical, circular or semicircular, angular, irregular, etc. In one embodiment, the aspect ratio (i.e., the ratio of length to width, where the length and width are measured perpendicular to each other and the length refers to the longest linear dimension) of the ionic or mixed ionic conductive oxide (e.g., metal-doped ceria) particles of each hybrid electrode particle may be 1.0 to 10.0, 1.0 to 5.0, or 1.0 to 2.0. In one embodiment, the aspect ratio of the ionic or mixed ionic conductive oxide (e.g., metal-doped ceria) particles of each hybrid electrode particle can be about 1.0 to 2.0, for example, the aspect ratio of the metal-doped ceria particles can be about 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0.

[0095] In some embodiments, the particle size (in nm) of the ionic or mixed ion conducting oxide particles per hybrid electrode particle is at least about 1, 2, 5, 10, 25, 50, 75, 100, 125, 150, 175, or 200. In some embodiments, the particle size (in nm) of the ionic or mixed ion conducting oxide particles per hybrid electrode particle is less than about 200, 175, 150, 125, 100, 75, 50, 25, 10, 5, 2, or 1. Combinations of any two or more of these higher and / or lower particle sizes are also possible, for example, the particle size (in nm) of the ionic or mixed ion conducting oxide particles per hybrid electrode particle is between about 1 and 200, 10 and 150, or 15 and 100. For example, the particle size (in nm) of the ionic or mixed ion conducting oxide particles per hybrid electrode particle is less than about 200, preferably less than about 100. In some embodiments, the particle size (in nm) of the metal-doped ceria particles per hybrid electrode particle is at least about 1, 2, 5, 10, 25, 50, 75, 100, 125, 150, 175, or 200. In some embodiments, the particle size (in nm) of the metal-doped ceria particles per hybrid electrode particle is less than about 200, 175, 150, 125, 100, 75, 50, 25, 10, 5, 2, or 1. Combinations of any two or more of these higher and / or lower particle sizes are also possible, for example, the particle size (in nm) of the metal-doped ceria particles per hybrid electrode particle is between about 1 and 200, 10 and 150, or 15 and 100. In a preferred embodiment, the particle size (in nm) of the ion or mixed ion conducting oxide particles per hybrid electrode particle is less than about 100. The particle size is taken as the longest cross-sectional diameter across the oxide particle. For non-spherical ionic or mixed ionic conducting oxide particles, the particle size is taken as the distance corresponding to the longest cross-sectional dimension across the particle. The particle size of the ionic or mixed ionic conducting oxide particles of each hybrid electrode particle can be measured by electron microscopy (e.g., TEM or SEM) or X-ray diffraction (e.g., Scherrer analysis of one or more diffraction peaks).

[0096] In some embodiments, the total amount of ions or mixed ion conducting oxides in the hybrid electrode particles (in % w / w, based on the total weight of the hybrid electrode particles) is at least 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of ions or mixed ion conducting oxides in the hybrid electrode particles is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, or 20. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the total amount of ions or mixed ion conducting oxides in the hybrid electrode particles can be between about 20% w / w and 50% w / w or about 25% and 45% w / w. In some embodiments, the total amount of ceria in the hybrid electrode particles (in % w / w, based on the total weight of the hybrid electrode particles) is at least 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of ceria in the hybrid electrode particles is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, or 20. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the total amount of ceria in the hybrid electrode particles may be between about 20% w / w and 50% w / w or about 25% and 45% w / w.

[0097] In some embodiments, the total amount of metal in the hybrid electrode particles is between about 20% w / w and 80% w / w, and the total amount of oxide in the hybrid electrode particles is between about 20% w / w and 50% w / w. In some embodiments, the total amount of metal in the hybrid electrode particles is between about 55% w / w and 75% w / w, and the total amount of oxide in the hybrid electrode particles is between about 25% w / w and 45% w / w.

[0098] In some embodiments, the total amount of silver in the hybrid electrode particles is between about 20% w / w and 80% w / w, and the total amount of cerium dioxide in the hybrid electrode particles is between about 20% w / w and 50% w / w. In some embodiments, the total amount of silver in the hybrid electrode particles is between about 55% w / w and 75% w / w, and the total amount of cerium dioxide in the hybrid electrode particles is between about 25% w / w and 45% w / w.

[0099] In some embodiments, the %w / w ratio of the metal to the oxide in the hybrid electrode particles is at least 1:10, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or 10:1. In some embodiments, the %w / w ratio of the metal to the oxide in the hybrid electrode particles is less than 10:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, or 10:1. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the %w / w ratio of the metal to the oxide in the hybrid electrode particles may be between about 1:5 and about 5:1 or about 1:2 and about 1:1. In some embodiments, the %w / w ratio of silver to cerium dioxide in the hybrid electrode particles is at least 1:10, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or 10:1. In some embodiments, the %w / w ratio of silver to ceria in the hybrid electrode particles is less than 10: 1, 5: 1, 4: 1, 3: 1, 2: 1, 1: 1, 1: 2, 1: 3, 1: 4, 1: 5, or 10: 1. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the %w / w ratio of silver to ceria in the hybrid electrode particles may be between about 1: 5 and about 5: 1 or about 1: 2 and about 1: 1.

[0100] It should be understood that multiple ion or mixed ion conducting oxide particles can be doped with one or more metal species. For example, ceria particles can be doped with gadolinium (Gd), samarium (Sm), praseodymium (Pr) or nickel (Ni). In another example, ferrite can be doped with titanium (Ti), cobalt (Co) and copper (Cu) or lanthanum strontium chromate, can be doped with manganese (Mn), calcium (Ca), bismuth (Bi), copper (Cu), ruthenium (Ru). One or more ceria particles can be doped with one or more metal species. The metal dopant can be provided by one or more metals selected from rare earth metals and alkaline earth metals.

[0101] In some embodiments, the metal dopant of the oxide particles can be provided by one or more of samarium (Sm), gadolinium (Gd), lanthanum (La), zirconium (Zr), yttrium (Y), ytterbium (Yb), erbium (Er), praseodymium (Pr), nickel (Ni), or by one or more of gadolinium (Gd), samarium (Sm) and yttrium (Y). In one embodiment, the metal dopant is gadolinium (Gd). It is noteworthy that the ions of gadolinium, samarium and cerium are similar in size and a large number of oxygen vacancies are generated. It has been found that the high concentration and high mobility of oxygen ion vacancies provide ionic or mixed ion conducting oxide (e.g., metal-doped ceria) particles with advantageously high ionic conductivity. However, it will also be understood that other metal dopants can also provide good ionic conductivity.

[0102] The metal dopant and the oxide are a single phase. The ratio of the metal dopant to the oxide in the ion or mixed ion conducting oxide particles can be between about 100: 1 and 2: 1, about 50: 1 and 3: 1, or 20: 1 and 4: 1. The ratio of the metal dopant to the oxide in the ion or mixed ion conducting oxide particles can be at least about 2: 1, 3: 1, 4: 1, 5: 1, 10: 1, 20: 1, 50: 1, or 100: 1. The ratio of the metal dopant to the oxide in the ion or mixed ion conducting oxide particles can be less than about 100: 1, 50: 1, 20: 1, 10: 1, 5: 1, 4: 1, 3: 1, or 2: 1. In one example, the metal dopant and ceria are a single phase. The ratio of the metal dopant to ceria in the metal-doped ceria particles can be between about 100: 1 and 2: 1, about 50: 1 and 3: 1, or 20: 1 and 4: 1. The ratio of the metal dopant to ceria in the metal-doped ceria particles may be at least about 2: 1, 3: 1, 4: 1, 5: 1, 10: 1, 20: 1, 50: 1, or 100: 1. The ratio of the metal dopant to ceria in the metal-doped ceria particles may be less than about 100: 1, 50: 1, 20: 1, 10: 1, 5: 1, 4: 1, 3: 1, or 2: 1.

[0103] The amount of metal dopant present in the ceria particles can be determined by the formula Ce 1-x M x O 2-δ Definition, wherein x is between about 0.01 to 0.3, 0.02 to 0.25 or 0.05 to 0.2, M is one or more metal dopants as defined above, and δ is between about 0.0 and 0.5 or 0.1 to 0.4. Combinations of any two of these higher and / or lower values ​​are also possible.

[0104] The amount of metal dopant in the oxide particles can vary. In some embodiments, the amount of metal dopant in the oxide particles (based on the total weight of the ion or mixed ion conducting oxide particles, in % w / w units) is at least about 1, 2, 5, 10, 15, 20, 25, 30, 40 or 50. In some embodiments, the amount of metal dopant in the oxide particles (based on the total weight of the ion or mixed ion conducting oxide particles, in % w / w units) is at least about 50, 40, 30, 25, 20, 15, 10, 5, 2 or 1. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the amount of metal dopant in the oxide particles can be between about 1% w / w and 35% w / w, about 2% w / w and 30% w / w, or 5% w / w and 25% w / w. In some embodiments, the amount of metal dopant in the oxide particles (in % w / w, based on the total weight of the ion or mixed ion conducting oxide particles) is about 1, 2, 5, 10, 15, 20, 25, 30, 40, or 50. In some embodiments, the amount of metal dopant in the ceria particles (in % w / w, based on the total weight of the metal-doped ceria particles) is at least about 1, 2, 5, 10, 15, 20, 25, 30, 40, or 50. In some embodiments, the amount of metal dopant in the ceria particles (in % w / w, based on the total weight of the metal-doped ceria particles) is at least about 50, 40, 30, 25, 20, 15, 10, 5, 2, or 1. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the amount of metal dopant in the cerium oxide particles can be between about 1% w / w and 35% w / w, about 2% w / w and 30% w / w, or 5% w / w and 25% w / w. In some embodiments, the amount of metal dopant in the cerium oxide particles (based on the total weight of the metal-doped cerium oxide particles, in % w / w units) is about 1, 2, 5, 10, 15, 20, 25, 30, 40, or 50.

[0105] In addition to the hybrid electrode particles, the electrode composition may further include one or more additives. In one embodiment, the electrode composition may further include a conductive additive. For example, the conductive additive may include one or more metal additives, such as nickel powder, titanium powder, stainless steel powder, and mixtures thereof.

[0106] Sintered electrode material

[0107] The electrode composition can be provided in the form of a sintered electrode material. As used herein, the term "sintered electrode material" refers to an electrode material produced by heating (e.g., firing) an electrode composition including hybrid electrode particles so that the metal particles of the hybrid electrode particles agglomerate and adhere to each other to form a continuous or semi-continuous metal metal phase within the electrode material of the solid oxide electrochemical cell.

[0108] The metal phase may include one or more metal parts. In some embodiments, the metal phase is a porous support. In one embodiment, the silver metal phase may include one or more silver metal parts. In some embodiments, the silver metal phase is a porous support. The porous nature is conducive to the transfer of mobile ion species throughout the electrode material. After sintering to form a metal phase (i.e., a support including a porous silver metal phase), the ion or mixed ion conductive oxide particles may remain in the form of discrete particles attached to the surface of the metal phase and / or may also adhere to other ions or mixed ion conductive oxide particles to form one or more discrete oxide phases (e.g., parts) attached to the surface of the metal phase. In one embodiment, the sintered electrode material includes a silver metal phase as a porous support and a plurality of discrete oxide phases dispersed in the silver metal phase. The discrete oxide phases may be in the form of metal-doped ceria particles.

[0109] Discrete oxide (e.g., metal-doped ceria) phases (e.g., particles or portions) may be dispersed within the metal (e.g., silver) phase. Without wishing to be bound by theory, the connection points at the interface between the metal phase surface and the discrete oxide phase provide multiple reactive sites throughout the sintered electrode material. The metal (e.g., silver) scaffold and the discrete oxide (metal-doped ceria) phase may facilitate the movement of electrons and / or mobile oxygen species (O 2- ) are transported to or from reactive sites located throughout the sintered electrode material, respectively, for example, when used as an electrode composition in a SOEC or SOFC. For example, due to the unique microstructure of the sintered electrode, ion and electron pathways are created to allow electrons and mobile oxygen species (O 2- ) is transferred to and from reactive sites located throughout the sintered electrode material. When the sintered electrode composition is used as an oxygen electrode in a solid oxide electrolysis cell (SOEC), the location of a reactive site in the sintered electrode material is Figure 3 Scanning electron microscopy images of sintered electrode compositions are also provided in Figure 4 , which shows a sintered silver phase including metal-doped ceria.

[0110] In some embodiments, the sintered electrode material may include3 The metal phase may include at least about 1, 2, 5, 10, 20, 50, 70, 100, 150, 200, 250, 300, 400, 500, 700, or 1000 discrete oxide phases. The sintered electrode material may include about 1, 2, 5, 10, 20, 50, 700, or 1000 discrete oxide phases per cm 3 The metal phase is less than about 1000, 700, 500, 400, 300, 250, 200, 150, 100, 70, 50, 20, 10, 5, 2, or 1 discrete oxide phase. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the sintered electrode material may include 100, 150, ...50, 100, 150, 150, 150, 150, 3 The metal phases are between about 10 and 100, 50 and 500, or 100 and 300 discrete oxide phases. In some embodiments, the sintered electrode material may include per cm 3 The silver metal phase may include at least about 1, 2, 5, 10, 20, 50, 70, 100, 150, 200, 250, 300, 400, 500, 700, or 1000 discrete metal-doped ceria phases. The sintered electrode material may include about 1, 2, 5, 10, 20, 50, 700, or 1000 discrete metal-doped ceria phases per cm 3 The silver metal phase is less than about 1000, 700, 500, 400, 300, 250, 200, 150, 100, 70, 50, 20, 10, 5, 2, or 1 discrete metal-doped ceria phase. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the sintered electrode material may include about 100, ... 3 The silver metal phase is between about 10 to 100, 50 to 500, or 100 to 300 discrete metal-doped ceria phases. It should be understood that the dispersion of discrete oxide (e.g., metal-doped ceria) phases within the metal (e.g., silver) phase can be determined by a range of instruments and methods, including spectroscopy and microscopy methods, such as scanning electron microscopy.

[0111] By sintering an electrode composition comprising hybrid electrode particles containing metal particles decorated with discrete oxide particles, an electrode material having improved dispersion of discrete oxide (e.g., metal-doped ceria) particles or phases dispersed throughout a porous metal (e.g., silver) scaffold is obtained, as opposed to conventional mixing and grinding methods in which separate metal particles and oxide particles are present in the composition, and this is evidenced by the resulting microstructure. It was surprisingly found that this sintering process provides an electrode material having enhanced electrical and ionic conductivity and catalytic activity for use as an electrode in a solid oxide battery cell (e.g., SOEC or SOFC). It should be understood that pre-sintering of the hybrid electrode particles also provides a microstructure showing metal (e.g., silver) particles decorated with oxide (e.g., ceria) particles, as opposed to separate particles or a heterogeneous mixture of metal particles coated with fine oxide particles such that the entire surface of the metal particles is covered with fine oxide particles.

[0112] In some embodiments, the size (in nm) of the discrete oxide particles / phases dispersed within the metal phase is at least about 1, 2, 5, 10, 25, 50, 75, 100, 125, 150, 175, 200, 400, 600, 800, or 1000. In some embodiments, the size (in nm) of the discrete oxide particles / phases dispersed within the metal phase is less than about 1000, 800, 600, 400, 200, 175, 150, 125, 100, 75, 50, 25, 10, 5, 2, or 1. Combinations of any two or more of these higher and / or lower particle sizes are also possible, for example, the size (in nm) of the discrete oxide particles / phases dispersed within the metal phase is about 1 to 600, 2 to 400, 3 to 200, or 4 to 100. In some embodiments, the size (in nm) of the discrete metal-doped ceria particles / phases dispersed within the silver metal phase is at least about 1, 2, 5, 10, 25, 50, 75, 100, 125, 150, 175, 200, 400, 600, 800, or 1000. In some embodiments, the size (in nm) of the discrete metal-doped ceria particles / phases dispersed within the silver metal phase is less than about 1000, 800, 600, 400, 200, 175, 150, 125, 100, 75, 50, 25, 10, 5, 2, or 1. Combinations of any two or more of these higher and / or lower particle sizes are also possible, for example, the size (in nm) of the discrete metal-doped ceria particles / phases dispersed within the silver metal phase is about 1 to 600, 2 to 400, 3 to 200, or 4 to 100. The size of oxide (eg, metal-doped ceria) phases / particles dispersed within a metal (eg, silver) phase can be measured by electron microscopy (eg, TEM or SEM) or X-ray diffraction (eg, Scherrer analysis of one or more diffraction peaks).

[0113] In some embodiments, the total amount of the metal phase in the sintered electrode material (in % w / w, based on the total weight of the sintered electrode material) is at least 10, 15, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of the metal phase in the sintered electrode material (in % w / w, based on the total weight of the sintered electrode material) is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, or 10. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the total amount of the metal phase in the sintered electrode material can be between about 20% w / w and 80% w / w or about 55% and 75% w / w. In some embodiments, the total amount of metallic phase in the sintered electrode material (in % w / w, based on the total weight of the sintered electrode material) is about 10, 15, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of silver metallic phase in the sintered electrode material (in % w / w, based on the total weight of the sintered electrode material) is at least 10, 15, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of silver metallic phase in the sintered electrode material (in % w / w, based on the total weight of the sintered electrode material) is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, or 10. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the total amount of silver metal phase in the sintered electrode material may be between about 20% w / w and 80% w / w or about 55% to 75% w / w. In some embodiments, the total amount of silver metal phase in the sintered electrode material (in % w / w, based on the total weight of the sintered electrode material) is about 10, 15, 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80.

[0114] In some embodiments, the total amount of oxides dispersed in the metal phase (in % w / w, based on the total weight of the sintered electrode material) is at least 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of oxides dispersed in the metal phase (in % w / w, based on the total weight of the sintered electrode material) is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, or 20. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the total amount of oxides dispersed in the metal phase can be between about 20% w / w and 50% w / w or about 25% and 45% w / w. In some embodiments, the total amount of oxides dispersed in the metal phase (based on the total weight of the sintered electrode material, in % w / w) is about 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75 or 80. In some embodiments, the total amount of metal phase in the sintered electrode material is between about 20% w / w and 80% w / w, and the total amount of oxides in the sintered electrode material is between about 20% w / w and 60% w / w. In some embodiments, the total amount of metal phase in the sintered electrode material is between about 55% w / w and 75% w / w, and the total amount of oxides in the sintered electrode material is between about 25% w / w and 45% w / w. In some embodiments, the total amount of ceria dispersed in the silver metal phase (in % w / w, based on the total weight of the sintered electrode material) is at least 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of ceria dispersed in the silver metal phase (in % w / w, based on the total weight of the sintered electrode material) is less than about 80, 75, 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, or 20. Combinations of any two or more of these higher and / or lower amounts are also possible, for example, the total amount of ceria dispersed in the silver metal phase can be between about 20% w / w and 80% w / w or about 25% and 45% w / w. In some embodiments, the total amount of ceria dispersed within the silver metal phase (in % w / w based on the total weight of the sintered electrode material) is about 20, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80. In some embodiments, the total amount of silver metal phase in the sintered electrode material is between about 20% w / w and 80% w / w, and the total amount of ceria in the sintered electrode material is between about 20% w / w and 60% w / w.In some embodiments, the total amount of silver metal phase in the sintered electrode material is between about 55% w / w and 75% w / w, and the total amount of cerium oxide in the sintered electrode material is between about 25% w / w and 45% w / w.

[0115] The thickness of the sintered electrode material can be selected to promote the electron and mobile ionic species (e.g., O 2- ) transport to and from reactive sites located throughout the electrode, the porosity, and the reactions of reactant species occurring within the electrode.

[0116] The sintered electrode material may have a certain degree of porosity. In some embodiments, the porosity of the sintered electrode material (based on the total volume of the sintered electrode material, in volume %) may be at least 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65 or 70. In some embodiments, the porosity of the sintered electrode material (based on the total volume of the sintered electrode material, in volume %) may be less than 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10 or 5. Combinations of any two or more of these higher porosity values ​​and / or lower porosity values ​​are also possible, for example, the porosity of the sintered electrode material can be between about 10 vol % to 60 vol %, about 20 vol % to 50 vol %, about 25 vol % to 45 vol %, or about 30 vol % to 40 vol %, based on the total volume of the sintered electrode material.

[0117] The porosity of the sintered electrode material can be determined by the density of the hybrid electrode particles in the electrode composition before sintering. The porosity can be determined by any suitable means, such as using a mercury porosimeter or by using an image analysis tool (such as ImageJ for viewing and measuring porosity by contrast) to perform electron microscopy image analysis on a cross section of the sintered electrode material.

[0118] The sintered electrode material may have any suitable thickness, which will depend on the sintering of the electrode composition comprising the hybrid electrode particles. The thickness of the sintered electrode material may be between any of the following ranges (in μm): about 10 and 2000, about 15 and 1000, about 20 and 500, about 25 and 400, about 30 and 300, about 40 and 200, or about 50 and 150. The thickness of the sintered electrode material is at least about 10 μm, 30 μm, 50 μm, 70 μm or 90 μm, 150 μm, 200 μm, 300 μm, 500 μm, 750 μm or 1000 μm. The thickness of the sintered electrode material may be less than about 2000 μm, 1500 μm, 1000 μm, 800 μm, 600 μm, 400 μm or 200 μm. The thickness of the sintered electrode material may be between any of the following ranges (in μm): about 1 and 100, about 5 and 80, about 5 to 70, about 10 to 50, or about 15 to 40. The thickness of the sintered electrode material is at least about 1 μm, 5 μm, 10 μm, 20 μm, 50 μm, 70 μm, 80 μm, or 100 μm. The thickness of the sintered electrode material may be less than about 100 μm, 80 μm, 70 μm, 50 μm, 20 μm, 10 μm, 5 μm, or 1 μm.

[0119] Coating preparation

[0120] The electrode composition can be a coating formulation, such as a liquid formulation, and the following examples and embodiments may be applicable to the coating formulation. The electrode composition or its sintered electrode material can be provided in the form of a coating formulation for commercial and industrial applications. The coating formulation can be prepared to apply the electrode composition or its sintered electrode material on the surface of a substrate as described in any of the examples or embodiments. The coating formulation can be prepared by dissolving or dispersing the electrode composition or its sintered electrode material according to any embodiment or example as described herein in a suitable solvent, and then optionally mixing the electrode composition with one or more additives (such as a binder), or dissolving the composition in a suitable solvent under suitable processing conditions. For example, the coating formulation can be a wet coating formulation including an electrode composition or its sintered electrode material, a solvent and an optional binder. An exemplary method is to first dissolve the binder in the solvent of the formulation, which can be accomplished by accompanying the use of heat and / or stirring. The electrode composition or its sintered electrode material can then be added, desirably at a progressive addition rate to avoid agglomeration. During the addition of the electrode composition or its sintered electrode material, heat and / or stirring can be applied again.

[0121] The wet coating formulation can be applied to a substrate (eg, a solid electrolyte) in different physical forms such as solutions, dispersions, suspensions, mixtures, aerosols, emulsions, pastes, or combinations thereof, with solutions or dispersions or emulsions being preferred.

[0122] In some embodiments, the wet coating formulation can be a dip coating formulation, a printable ink formulation or a brush printing formulation. The wet coating formulation can be a dip coating formulation. The wet coating formulation can be a printable ink formulation. The wet coating formulation can be a brush printing formulation. Any solvent that can dissolve / suspend the electrode composition or its sintered electrode material and the binder in the coating formulation can be used. The solvent can be a single solvent or a mixture of solvents that dissolves the binder and can evaporate when dried under mild drying conditions (e.g., about 50° C. to about 250° C.) after dip coating. The solvent can be an alcohol, ester, terpene, ketone, aliphatic, aromatic, ether or water, including mixtures thereof. In one embodiment, the solvent can be an alcohol. Suitable alcohol solvents include monohydric alcohols, dihydric alcohols (such as glycols), ether alcohols and terpene alcohols. Examples include methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, hexanol, heptanol, cyclohexanol, butyl glycol, diols (such as ethylene glycol), propylene glycol, diethylene glycol, triethylene glycol, ether alcohols (such as butoxyethanol, propoxypropanol and butyl diglycol) and terpene alcohols (such as terpineol (α-terpineol), β-terpineol, geraniol, eucalyptol, cedrol, linalool, 4-terpineol, lavandulol, citronellol or nerol. In one example, ethanol can be a preferred solvent. In another example, a mixture of one or more solvents can be used, for example, a mixture of ethanol and α-terpineol.

[0123] The coating formulation may include at least about 1, 2, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50% w / w of solvent, based on the total weight of the formulation. The coating formulation may include less than about 50, 45, 40, 35, 30, 25, 20, 15, 10, 5, 2, or 1% w / w of solvent, based on the total weight of the formulation. Combinations of these amounts are also possible, such as between about 25% w / w and about 45% w / w. In some embodiments, the coating formulation includes a monohydric alcohol solvent (e.g., ethanol) in an amount between about 20% w / w and 40% w / w and a terpene alcohol solvent (e.g., α-terpineol) in an amount between about 1% w / w and about 10% w / w, based on the total weight of the coating formulation.

[0124] Any suitable adhesive can be used to prepare the coating formulation. In one embodiment, the adhesive can be polyvinyl butyral, polyvinyl alcohol, polyacrylate, polymethyl methacrylate or ethyl cellulose. Based on the gross weight of the preparation, the coating formulation can include an amount of at least about 1,2,3,4,5,6,8,10,15 or 20 adhesives (% w / w). Based on the gross weight of the preparation, the coating formulation can include an amount of less than about 20,15,10,8,6,5,4,3,2 or 1 adhesives (% w / w)). The combination of these amounts is also possible, for example, between about 1% w / w to about 5% w / w.

[0125] In some embodiments or examples, the thickness of the coating formulation can be in the range of about 1 μm to about 100 μm. The thickness (in μm) can be less than about 100, 80, 60, 40, 20, 15, 10, 8, 6, 4, 2 or 1. The thickness (in μm) can be at least about 1, 2, 4, 6, 8, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90 or 100. The thickness (μm) of the coating formulation can be provided by any two of these higher values ​​and / or lower values. For example, the thickness of the coating formulation can be about 50 μm. The thickness of the coating formulation can be selected to promote the movement of electrons and mobile ionic species (e.g., O 2- ) transport to and from reactive sites located throughout the electrode, the porosity, and the reactions of reactant species occurring within the electrode.

[0126] The coating formulation may have a certain degree of porosity. In some embodiments, the porosity of the coating formulation (based on the total volume of the coating formulation, in volume %) may be at least 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65 or 70. In some embodiments, the porosity of the coating formulation (based on the total volume of the sintered electrode material, in volume %) may be less than 70, 65, 60, 55, 50, 45, 40, 35, 30, 25, 20, 15, 10 or 5. Any combination of two or more of these higher porosity values ​​and / or lower porosity values ​​is also possible, for example, based on the total volume of the sintered electrode material, the porosity of the coating formulation may be between about 10% to 60% by volume, about 20% to 50% by volume, about 25% to 45% by volume or about 30% to 40% by volume.

[0127] The porosity of the coating formulation can be determined by the density of the hybrid electrode particles in the electrode composition before sintering. The porosity can be determined by any suitable means, such as using a mercury porosimeter or by performing electron microscopy image analysis on a cross section of the coating formulation using an image analysis tool such as ImageJ for viewing and measuring porosity by contrast.

[0128] Method for preparing hybrid electrode particles

[0129] The present invention also identifies an improved sol-gel process that can be used to prepare hybrid electrode particles. By controlling the reaction conditions and reagents of the improved sol-gel process, the stoichiometry of silver and ceria of the hybrid electrode particles can be finely tuned, thereby producing an electrode composition including hybrid electrode particles with improved electrical, ionic and / or catalytic properties.

[0130] The hybrid electrode particles can be prepared by a modified sol-gel method. As used herein, the term "modified sol-gel method" refers to the synthesis of solid materials from solution precursors and involves converting monomers into a colloidal solution (i.e., a sol) and then heating the colloidal solution to obtain a solid material, which serves as a precursor to a discrete particle network (or gel). An example of this process is the Pechini method.

[0131] An improved sol-gel method for preparing hybrid electrode particles, wherein each hybrid electrode particle comprises at least one metal phase and one oxide phase, wherein the metal phase comprises a plurality of metal particles, and the oxide phase comprises a plurality of ion- or mixed-ion-conducting oxide particles on the surface of the metal particles, wherein the plurality of ion- or mixed-ion-conducting oxide particles decorate the surface of the metal particles, and wherein the particle size (in nm) of the ion- or mixed-ion-conducting oxide particles on the surface of the metal particles is between about 1 and 100, wherein the method comprises:

[0132] a) preparing a gel from an aqueous solution comprising a metal species, an ion or mixed ion conducting oxide species, a plasticizer and a chelating agent; and

[0133] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0134] In another embodiment, the improved sol-gel method for preparing hybrid electrode particles comprises:

[0135] a) preparing a gel from an aqueous solution comprising a silver metal species, a cerium metal species, a metal dopant species, a plasticizer, and a chelating agent; and

[0136] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0137] In another embodiment, the improved sol-gel method for preparing hybrid electrode particles, wherein the method comprises:

[0138] a) preparing a gel from an aqueous solution comprising a bimetallic metal species, a cerium metal species, a metal dopant species, a plasticizer, and a chelating agent; and

[0139] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0140] In another embodiment, the improved sol-gel method for preparing hybrid electrode particles, wherein the method comprises:

[0141] a) preparing a gel from an aqueous solution comprising a bimetallic metal species, a metal-doped ferrite, a plasticizer and a chelating agent; and

[0142] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0143] Metal species

[0144] One or more of the metal species (e.g., cerium, silver, etc.) and the metal dopant species can be provided in the form of a salt or its hydrate. In one embodiment, the metal species and the metal dopant species are cationic (i.e., ionic salts or their hydrates). The metal species and the metal dopant species should be soluble or miscible in aqueous solution alone or in the presence of a chelating agent. Therefore, typical salts include hydroxides, alcohol oxides, acetates, chlorides, citrates and nitrates, wherein nitrates are preferred.

[0145] The metal (e.g., silver) species can be provided in the form of any suitable salt or hydrate thereof, the salt or hydrate thereof being independently selected from hydroxides, chlorides, alcohol oxides, acetates, citrates, nitrates, and oxide salts. In some embodiments, the silver metal species can be provided in the form of silver nitrate (AgNO3), silver chloride (AgCl), silver hydroxide (AgOH), or silver oxide (Ag2O), or a hydrate thereof.

[0146] The metal (e.g., cerium) species can be provided in the form of any suitable salt or hydrate thereof, the salt or hydrate thereof being independently selected from hydroxides, chlorides, alcohol oxides, acetates, citrates, nitrates, and oxide salts. In certain embodiments, the cerium metal species can be provided in the form of cerium nitrate (Ce(NO3)3), cerium chloride (CeCl3), cerium hydroxide (Ce(OH)3) or cerium oxide (Ce2O3) or a hydrate thereof. Examples of suitable hydrates include hexahydrate salts, such as hexahydrate cerium nitrate (Ce(NO3)3.6H2O).

[0147] In one embodiment, the inventors unexpectedly discovered that a combination of silver nitrate (AgNO3) and cerium nitrate (Ce(NO3)3) can produce hybrid electrode particles with improved conductivity and catalytic activity. It is understood that the improved conductivity and catalytic activity may be due to the resulting microstructure showing silver particles decorated with nanocrystalline cerium dioxide particles. However, other salt forms, including cerium chloride (CeCl3), can also produce hybrid electrode particles with similar properties and / or microstructures.

[0148] In another embodiment, the inventors unexpectedly discovered that the combination of silver nitrate (AgNO3) and iron nitrate nonhydrate as metal species with doped cerium nitrate (Ce(NO3)3) as a mixed oxide phase can produce hybrid electrode particles with improved conductivity and catalytic activity. It is understood that the improved conductivity and catalytic activity may be caused by the resulting microstructure showing bimetallic metal particles decorated with nanocrystalline ceria particles.

[0149] In other embodiments, the inventors unexpectedly discovered that a combination of silver nitrate (AgNO3) as a metal species with lanthanum nitrate hexahydrate, strontium nitrate, cobalt nitrate hexahydrate, and non-aqueous iron nitrate as mixed oxide phases can produce hybrid electrode particles with improved conductivity and catalytic activity. It is understood that the improved conductivity and catalytic activity may be due to the resulting microstructure showing bimetallic metal particles decorated with a lanthanum strontium doped ferrite phase.

[0150] The metal dopant species can be provided in the form of any suitable salt or hydrate thereof. In some embodiments, the metal dopant species can be selected from rare earth metal salts or alkaline earth metal salts or hydrates thereof. In some embodiments, the metal dopant species can be provided by one or more metal salts or hydrates selected from the following: samarium (Sm) salts, gadolinium (Gd) salts, lanthanum (La) salts, zirconium (Zr) salts, yttrium (Y) salts, ytterbium (Yb) salts, erbium (Er) salts, praseodymium (Pr) salts or neodymium (Nd) salts or hydrates thereof. The salt can be any one or more of nitrates, chlorides, hydroxides or oxides. In some embodiments, the metal dopant species can be provided by one or more nitrates of the following: samarium (Sm) salts, gadolinium (Gd) salts, lanthanum (La) salts, zirconium (Zr) salts, yttrium (Y) salts, ytterbium (Yb) salts, erbium (Er) salts, praseodymium (Pr) salts or neodymium (Nd) salts or hydrates thereof. In some embodiments, the metal dopant species may be provided by nitrates of gadolinium (Gd), samarium (Sm), and yttrium (Y), or hydrates thereof.

[0151] In one embodiment, the metal dopant species may be provided by gadolinium nitrate (Gd(NO3)3) or a hydrate thereof, such as gadolinium nitrate hexahydrate (Gd(NO3)3.6H2O). The inventors have identified that, because the ionic size of gadolinium is similar to that of cerium, a large amount of metal doping can occur within the ceria particles using gadolinium nitrate, thereby allowing efficient integration of gadolinium into the ceria network.

[0152] In some embodiments, the oxide species and the metal dopant species can each be provided in the aqueous solution at a concentration of at least about 0.01 M, 0.02 M, 0.03 M, 0.04 M, 0.05 M, 0.06 M, 0.07 M, 0.08 M, 0.09 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, or 1.0 M. In some embodiments, the oxide species and the metal dopant species can each be provided in the aqueous solution at a concentration of less than about 1.0 M, 0.5 M, 0.4 M, 0.3 M, 0.2 M, 0.1 M, 0.09 M, 0.08 M, 0.07 M, 0.06 M, 0.05 M, 0.04 M, 0.03 M, 0.02 M, or 0.01 M. Combinations of any two or more of these higher concentrations and / or lower concentrations are also possible, for example, the oxide species and the metal dopant species can each be provided in the aqueous solution at a concentration between about 0.01 M to 0.05 M or 0.01 M to 0.1 M. In some embodiments, the oxide species and the metal dopant species can each be provided in the aqueous solution at a concentration of about 0.01 M, 0.02 M, 0.03 M, 0.04 M, 0.05 M, 0.06 M, 0.07 M, 0.08 M, 0.09 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M or 1.0 M.

[0153] In some embodiments, the cerium metal species and the metal dopant species can each be provided in the aqueous solution at a concentration of at least about 0.01 M, 0.02 M, 0.03 M, 0.04 M, 0.05 M, 0.06 M, 0.07 M, 0.08 M, 0.09 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, or 1.0 M. In some embodiments, the cerium metal species and the metal dopant species can each be provided in the aqueous solution at a concentration of less than about 1.0 M, 0.5 M, 0.4 M, 0.3 M, 0.2 M, 0.1 M, 0.09 M, 0.08 M, 0.07 M, 0.06 M, 0.05 M, 0.04 M, 0.03 M, 0.02 M, or 0.01 M. Combinations of any two or more of these higher concentrations and / or lower concentrations are also possible, for example, the cerium metal species and the metal dopant species can each be provided in the aqueous solution at a concentration between about 0.01 M to 0.05 M or 0.01 M to 0.1 M. In some embodiments, the cerium metal species and the metal dopant species can each be provided in the aqueous solution at a concentration of about 0.01 M, 0.02 M, 0.03 M, 0.04 M, 0.05 M, 0.06 M, 0.07 M, 0.08 M, 0.09 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M or 1.0 M.

[0154] In some embodiments, the metal species can be provided in an aqueous solution at a concentration of at least about 0.01M, 0.02M, 0.03M, 0.04M, 0.05M, 0.06M, 0.07M, 0.08M, 0.09M, 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, or 1.0M. The concentration can be selected based on the desired w / w % of the metal in the final hybrid electrode particles. In some embodiments, the metal species can be provided in an aqueous solution at a concentration of less than about 1.0M, 0.5M, 0.4M, 0.3M, 0.2M, 0.1M, 0.09M, 0.08M, 0.07M, 0.06M, 0.05M, 0.04M, 0.03M, 0.02M, or 0.01M. Combinations of any two or more of these higher concentrations and / or lower concentrations are also possible, for example, the metal species may be provided in a concentration between about 0.01 M and 0.1 M in the aqueous solution.

[0155] In some embodiments, the silver metal species can be provided in an aqueous solution at a concentration of at least about 0.01M, 0.02M, 0.03M, 0.04M, 0.05M, 0.06M, 0.07M, 0.08M, 0.09M, 0.1M, 0.2M, 0.3M, 0.4M, 0.5M, or 1.0M. The concentration can be selected based on the desired w / w % of silver in the final hybrid electrode particles. In some embodiments, the silver metal species can be provided in an aqueous solution at a concentration of less than about 1.0M, 0.5M, 0.4M, 0.3M, 0.2M, 0.1M, 0.09M, 0.08M, 0.07M, 0.06M, 0.05M, 0.04M, 0.03M, 0.02M, or 0.01M. Combinations of any two or more of these higher and / or lower concentrations are also possible, for example, the silver metal species may be provided in a concentration between about 0.01 M and 0.1 M in the aqueous solution.

[0156] In some embodiments, the molar ratio of the metal species to the oxide species can be at least about 1:10, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or 10:1. In some embodiments, the molar ratio of the metal species to the oxide species can be less than about 10:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, or 1:10. Combinations of any two or more of these higher and / or lower ratios are also possible, for example, the molar ratio of the metal species to the oxide species can be between about 1:5 to about 5:1 or about 1:2 to 1:1.

[0157] In some embodiments, the molar ratio of the silver metal species to the cerium metal species can be at least about 1:10, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, or 10:1. In some embodiments, the molar ratio of the silver metal species to the cerium metal species can be less than about 10:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, or 1:10. Combinations of any two or more of these higher and / or lower ratios are also possible, for example, the molar ratio of the silver metal species to the cerium metal species can be between about 1:5 to about 5:1 or about 1:2 to 1:1.

[0158] The inventors have discovered that the ratio of metal species to oxide species is important for controlling the amount of ions or mixed ion-conducting oxides present in the hybrid electrode particles. In particular, according to at least some embodiments or examples, it is advantageous to retain at least a portion of the surface of the metal particles free of oxide particles to allow interaction with the metal surface on the adjacent hybrid electrode particles, thereby providing electronic conduction, and the other portion provides a plurality of oxide particles. The inventors unexpectedly identified that a ratio of metal species to oxide species between about 2:1 and 1:1 can provide an enhanced level of oxide decoration while retaining sufficient area of ​​the metal particle surface free to interact with the metal surface on the adjacent particles.

[0159] The inventors have discovered that the ratio of silver species to metal species is important for controlling the amount of ceria present in the hybrid electrode particles. In particular, according to at least some embodiments or examples, it is advantageous to retain at least a portion of the surface of the silver particles free of ceria to allow interaction with the silver surface on the adjacent hybrid electrode particles, thereby providing electronic conduction, and the other portion provides a plurality of ceria particles. The inventors unexpectedly identified that a ratio of silver species to metal species between about 2:1 and 1:1 can provide an enhanced level of ceria decoration while retaining sufficient area of ​​the silver particle surface free to interact with the silver surface on the adjacent particles. For example, electrodes prepared with 70 wt.% of silver and 30 wt.% of a mixed ion-conducting phase show higher performance, as shown in at least one of the examples provided herein.

[0160] In some embodiments, the molar ratio of the metal dopant species to the oxide species is at least about 1:100, 1:80, 1:50, 1:20, 1:10, 1:5, or 1:1. In some embodiments, the molar ratio of the metal dopant species to the oxide species is less than about 1:1, 1:5, 1:10, 1:20, 1:50, 1:80, or 1:100. Combinations of any two or more of these higher and / or lower ratios are also possible, for example, the molar ratio of the metal dopant species to the oxide species may be between about 1:50 and 1:1. In some embodiments, the molar ratio of the metal dopant species to the oxide species is about 1:100, 1:80, 1:50, 1:20, 1:10, 1:5, or 1:1.

[0161] In some embodiments, the molar ratio of the metal dopant species to the cerium metal species is at least about 1:100, 1:80, 1:50, 1:20, 1:10, 1:5, or 1:1. In some embodiments, the molar ratio of the metal dopant species to the cerium metal species is less than about 1:1, 1:5, 1:10, 1:20, 1:50, 1:80, or 1:100. Combinations of any two or more of these higher and / or lower ratios are also possible, for example, the molar ratio of the metal dopant species to the cerium metal species may be between about 1:50 and 1:1. In some embodiments, the molar ratio of the metal dopant species to the cerium metal species is about 1:100, 1:80, 1:50, 1:20, 1:10, 1:5, or 1:1.

[0162] Chelating agents

[0163] The chelating agent can be any suitable compound that can coordinate with the silver metal species, the cerium metal species and / or the metal dopant species while providing one or more functional groups that can crosslink with the plasticizer (e.g., by esterification) to produce a gel including the silver metal species, the cerium metal species and the metal dopant species. In one embodiment, the same chelating agent is used to individually chelate each of the silver metal species, the cerium metal species and the metal dopant species. Alternatively, different chelating agents can be used, which can be selected based on their chelating affinity for one or more metal species.

[0164] In some embodiments, the chelating agent is selected from carboxylic acids, amines, amino acids, amino polycarboxylic acids, diesters, β-diketones, β-ketoesters, and any combination thereof. Suitable carboxylic acids include dicarboxylic acids, tricarboxylic acids, or tetracarboxylic acids (e.g., compounds including 2, 3, or 4 carboxylic acid groups), including, for example, citric acid, lactic acid, glycolic acid, malonic acid, tartaric acid, succinic acid, glutaric acid, or malic acid, and any combination thereof. Suitable amino acids include glycine, methionine, lysine, or glycine, and any combination thereof. Suitable amino polycarboxylic acids include ethylenediaminetetraacetic acid (EDTA), iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), diethyltriaminepentaacetic acid (DTPA), or 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA), and any combination thereof. In one embodiment, the chelating agent is selected from citric acid, glycine, or EDTA, and any combination thereof. Specifically, it was found that citric acid and EDTA were particularly effective chelating agents for forming hybrid electrode particles.

[0165] In some embodiments, the molar ratio of the chelating agent to the metal species (e.g., silver metal species, cerium metal species, and metal dopant species) present in the aqueous solution is at least about 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, or 5:1. In some embodiments, the molar ratio of the chelating agent to the metal species in the aqueous solution is less than about 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, or 1:5. Combinations of any two or more of these higher and / or lower ratios are also possible, for example, the molar ratio of the chelating agent to the metal species present in the aqueous solution can be between about 1:5 to about 5:1 or about 1:2 to about 2:1. The inventors have found that a ratio of about 1:1 to 1:5 (e.g., 1:2) of the chelating agent to the metal species present in the aqueous solution can provide additional advantages, such as forming a stable chelated aqueous solution with the metal species, which can produce a stable solution with minimal or no observed precipitation.

[0166] Plasticizers

[0167] In order to form a gel in step a), the chelating agent chelates the metal species and is subsequently cross-linked with the plasticizer to form a covalent network in the form of a gel, such as by esterification. One or more advantages are associated with forming a gel as described herein, and the one or more advantages include stabilizing and fixing the metal species to prevent segregation, which allows the synthesis of homogeneously doped metal oxides (e.g., gadolinium-doped cerium oxide). Therefore, the plasticizer can be any suitable compound capable of cross-linking the chelate in the aqueous solution. Cross-linking can occur by any suitable reaction between the functional groups on the chelating agent and the plasticizer, such as by esterification (e.g., polyols and carboxylic acids) or amidation (amines and carboxylic acids).

[0168] In one embodiment, the plasticizer can be a polyol (i.e., polyalcohol). The plasticizer can be a glycol. Suitable glycols include ethylene glycol, diethylene glycol, propylene glycol, butylene glycol and triethylene glycol and combinations thereof. In one embodiment, the plasticizer is selected from ethylene glycol, diethylene glycol and triethylene glycol and mixtures thereof. According to some embodiments or examples, the inventors have found that diol plasticizers are easy to form gels with carboxylic acid chelating agents (e.g., citric acid) by esterification to form stable gels including one or more metal species described herein, which is highlighted by example below (image from Dimesso L. (2018) Pechini Processes: An Alternate Approach of the Sol-Gel Method, Preparation, Properties, and Applications. In: Klein L., Aparicio M., Jitianu A. (eds.) Handbook of Sol-Gel Science and Technology. Springer, Cham. https: / / doi.org / 10.1007 / 978-3-319-32101-1_123):

[0169]

[0170] In some embodiments, the molar ratio of the plasticizer to the metal species (e.g., silver metal species, cerium metal species, and metal dopant species) present in the aqueous solution is at least about 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, or 8:1. In some embodiments, the molar ratio of the plasticizer to the metal species in the aqueous solution is less than about 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, or 1:5. Combinations of any two or more of these higher and / or lower ratios are also possible, for example, the molar ratio of the plasticizer to the metal species present in the aqueous solution can be between about 1:1 to about 6:1, about 1:1 to about 4:1. In some embodiments, the molar ratio of the plasticizer to the metal species present in the aqueous solution is about 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, or 8:1. The inventors have discovered that a ratio of about 1:1 to 5:1 (e.g., about 2:1 to 4:1) of plasticizer to metal species present in the aqueous solution provides a plasticizer-rich aqueous solution that is easily cross-linked with a chelating agent to form a stable gel including the metal species.

[0171] In some embodiments, the molar ratio of plasticizer to chelator in the aqueous solution is at least about 1:1, 2:1, 3:1, 4:1, or 5:1, such as at least about 2:1 (eg, 2 plasticizer compounds per 1 chelate).

[0172] Aqueous solutions and gels including metal species

[0173] Depending on the degree of crosslinking between the plasticizer and the chelating agent present in the aqueous solution, the aqueous solution may be viscous but flowable before forming a gel at step a). The aqueous solution used to prepare the gel at step a) may be prepared using any suitable aqueous medium such as water (e.g., deionized water).

[0174] The pH of the aqueous solution can be adjusted to promote the chelation of one or more metal species, control the polymerization of chelating agents and plasticizers and / or prevent the precipitation of one or more metal species. The pH can be controlled by adding any suitable alkali or acid. For example, in order to increase the pH of the aqueous solution to a more alkaline (i.e., lower acidity) pH, a suitable alkali can be added to the aqueous solution. Suitable alkali can include urea, ammonium or ammonium hydroxide. In order to reduce the pH of the aqueous solution to a more acidic (i.e., lower alkalinity) pH, a suitable acid can be added to the aqueous solution. Suitable acid can include nitric acid.

[0175] The pH of the aqueous solution may be adjusted by adding a suitable acid or base to achieve a pH of at least about pH 3, 3.5, 4, 4.5, 5, 5.5, 6, or 7. The pH of the aqueous solution may be adjusted by adding a suitable acid or base to achieve a pH of less than about pH 7, 6.5, 6, 5.5, 5, 4.5, 4, 3.5, or 3. Combinations of any two or more of these higher pH values ​​and / or lower pH values ​​are also possible, for example between about pH 3 to about pH 7.

[0176] The gel can be formed spontaneously from an aqueous solution comprising a silver metal species, a cerium metal species, a metal dopant species, a plasticizer, and a chelating agent. For example, polyesterification of excess carboxylic acid groups of a chelating agent with a polyol plasticizer can occur spontaneously in aqueous solution.

[0177] In certain embodiments, the aqueous solution can be aged at a certain time period and a suitable temperature at step a) to promote the crosslinking between plasticizer and chelating agent, for example, to help polyesterification, to form a gel. In certain embodiments, the aqueous solution is aged for at least about 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 36 hours or 48 hours, to form a gel. The aqueous solution can be aged for a time period less than about 48 hours, 36 hours, 24 hours, 18 hours, 12 hours, 10 hours, 8 hours or 6 hours, to form a gel. Any two or more combinations of these higher aging times and / or lower aging times are also possible, for example, the aqueous solution is aged for a time period between about 12 hours to 36 hours before forming a gel, thereby providing uniform structure and phase consistency. In certain embodiments, the aqueous solution is aged for about 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 36 hours or 48 hours, to form a gel. In one embodiment, the aqueous solution can be aged for about 24 hours to 36 hours before heating at step b).

[0178] In some embodiments, the aqueous solution can be aged at a temperature of at least about 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., or 95° C. to form a gel. In some embodiments, the aqueous solution can be aged at a temperature of less than about 95° C., 90° C., 85° C., 80° C., 75° C., 70° C., 65° C., or 60° C. to form a gel. Combinations of any two or more of these higher aging temperatures and / or lower aging temperatures are also possible.

[0179] It should be understood that any combination of two or more of the above aging temperature times is also possible, for example, the aqueous solution can be aged for a period of time between about 12 hours and 36 hours and at a temperature between about 65°C and 90°C to form a gel.

[0180] The aging of the aqueous solution at step a) can be a two-step aging process. In one embodiment, the aqueous solution is aged at a first temperature and for a time period effective to promote crosslinking between the plasticizer and the chelating agent (e.g., to aid polyesterification and / or remove any residual aqueous solution), and then cooled to a second temperature and aged for a time period effective to form a gel. For example, the process can include (i) aging the aqueous solution at a first temperature and for a time period effective to promote crosslinking between the plasticizer and the chelating agent (e.g., to aid polyesterification and / or remove any residual aqueous solution), and then (ii) cooling to a second temperature and aging at the cooled second temperature for a time period effective to form a gel.

[0181] For step (i), the aqueous solution can be aged at a temperature of at least about 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C. The aging temperature at step (i) can be less than about 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C or 60°C to form a gel. Combinations of any two or more of these higher aging temperatures and / or lower aging temperatures are also possible, for example between about 65°C to 90°C or about 70°C to 85°C. For step (i), the aqueous solution can be aged for a period of at least about 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 36 hours or 48 hours. The aging at step (i) can last for a period of less than about 48 hours, 36 hours, 24 hours, 18 hours, 12 hours, 10 hours, 8 hours or 6 hours. Combinations of any two or more of these higher aging times and / or lower aging times are also possible, such as between about 12 hours and 36 hours, such as 24 hours. It should be understood that combinations of any two or more of the above aging temperature times are also possible, such as at step (i), the aqueous solution can be aged over a period of time between about 12 hours and 36 hours and at a temperature between about 65° C. and 95° C.

[0182] For step (ii), the aqueous solution can be cooled to a temperature lower than the aging temperature at step (i). For example, in step (ii), the aqueous solution can be cooled to a temperature of at least about 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 50°C, or 60°C. At step (ii), the aqueous solution can be cooled to a temperature less than about 60°C, 50°C, 40°C, 35°C, 30°C, 25°C, 20°C, 15°C, 10°C, or 5°C. Combinations of any two or more of these higher cooling aging temperatures and / or lower cooling aging temperatures are also possible, such as between about 5°C and 40°C or about 10°C and 30°C, such as room temperature. For step (ii), the aqueous solution can be aged at a cooling temperature for a period of at least about 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 36 hours, or 48 hours. The aging at step (i) can last for a period of less than about 48 hours, 36 hours, 24 hours, 18 hours, 12 hours, 10 hours, 8 hours, 6 hours or 4 hours. Any combination of two or more of these higher aging times and / or lower aging times is also possible, for example, between about 2 hours to 12 hours or about 4 hours to 8 hours. It should be understood that any combination of two or more of the above aging temperature times is also possible, for example, at step (ii), the aqueous solution can be aged in a period of about 4 hours to 8 hours and at a temperature between about 10° C. to 30° C.

[0183] In some embodiments, after step a) but before step b), the gel may also be aged for a period of time and at a suitable temperature prior to heating at step b) to further promote crosslinking between the plasticizer and the chelating agent, for example to aid polyesterification and / or remove any residual aqueous solution. It should be understood that this aging step is different from heating the gel (e.g., pyrolysis) at step b) to obtain a powder composition including hybrid electrode particles. One or more advantages of aging the gel may include further stabilizing and / or promoting crosslinking between the plasticizer and the chelating agent, thereby providing a uniform microstructure and / or phase consistency.

[0184] In one embodiment, the aging of the gel before step b) is carried out at a lower temperature than the temperature at which the gel is heated at step b) to obtain a powder composition (i.e., an electrode composition as described herein) comprising hybrid electrode particles. In some embodiments, the gel formed in step a) is aged for a period of at least about 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 36 hours, or 48 hours before the heating at step b). The gel formed in step a) may be aged for a period of less than about 48 hours, 36 hours, 24 hours, 18 hours, 12 hours, 10 hours, 8 hours, or 6 hours before the heating at step b). Any combination of two or more of these higher aging times and / or lower aging times is also possible, such as a period of about 12 hours to 48 hours or about 24 hours to 48 hours before the heating at step b) of the gel formed in step a). In some embodiments, the gel formed in step a) is aged for a period of about 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, 24 hours, 36 hours, or 48 hours before the heating at step b). In one embodiment, the gel formed in step a) may be aged for a period of between about 24 hours and 48 hours prior to heating at step b).

[0185] In some embodiments, the gel formed in step a) may be aged at a temperature of at least about 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or 95°C prior to heating at step b). In some embodiments, the gel formed in step a) may be aged at a temperature of less than about 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, or 60°C prior to heating at step b). Combinations of any two or more of these higher aging temperatures and / or lower aging temperatures are also possible, such as the gel formed in step a) being aged at a temperature between about 65°C to 90°C or about 70°C to 85°C prior to heating at step b). In some embodiments, the gel formed in step a) may be aged at a temperature of about 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, or 95°C prior to heating at step b). It should be understood that any combination of two or more of the above aging temperature times is also possible, for example, the gel formed in step a) can be aged for a period of time between about 12 hours and 36 hours and at a temperature between about 60°C and 90°C before heating at step b).

[0186] The aging described above can be performed using any conventional oven such as a laboratory drying oven or a convection oven. In one embodiment, aging is performed by drying (eg, in a laboratory drying oven or a conventional oven).

[0187] In one embodiment, step a) comprises preparing an aqueous solution comprising an oxide species and a metal dopant species, followed by adding a chelating agent, a plasticizer to the aqueous solution, and then adding the metal species to the aqueous solution.

[0188] In one embodiment, step a) comprises preparing an aqueous solution comprising a cerium metal species and a metal dopant species, followed by adding a chelating agent, a plasticizer to the aqueous solution, and then adding a silver metal species to the aqueous solution.

[0189] In a further embodiment, the aqueous solution comprising oxide species, metal dopant species, chelating agent and plasticizer is aged prior to adding the metal species. In a further embodiment, the aqueous solution comprising cerium metal species, metal dopant species, chelating agent and plasticizer is aged prior to adding the silver metal species. This aging step can be performed at any temperature and time period as described above for the gel, for example, the aqueous solution is aged at a temperature between about 65°C to 90°C or about 70°C to 85°C for 12 hours to 36 hours prior to adding the silver metal species. This will form an intermediate gel / viscous aqueous solution prior to adding the metal species (e.g., silver). Alternatively, the metal species are added to the aqueous solution prior to any aging step.

[0190] Metal species can be added to the aqueous solution including oxide species, metal dopant species, chelating agent and plasticizer in the form of aqueous solution. Silver metal species can be added to the aqueous solution including cerium metal species, metal dopant species, chelating agent and plasticizer in the form of aqueous solution. The aqueous solution including metal species can be added dropwise to the aqueous solution including oxide species, metal dopant species, chelating agent and plasticizer. The aqueous solution including silver metal species can be added dropwise to the aqueous solution including cerium metal species, metal dopant species, chelating agent and plasticizer. In certain embodiments, metal species can be provided in the aqueous solution with a concentration of at least about 0.01M, 0.02M, 0.03M, 0.04M, 0.05M, 0.06M, 0.07M, 0.08M, 0.09M, 0.1M, 0.2M, 0.3M, 0.4M, 0.5M or 1.0M. In some embodiments, the metal species can be provided in the aqueous solution at a concentration of less than about 1.0 M, 0.5 M, 0.4 M, 0.3 M, 0.2 M, 0.1 M, 0.09 M, 0.08 M, 0.07 M, 0.06 M, 0.05 M, 0.04 M, 0.03 M, 0.02 M, or 0.01 M. Combinations of any two or more of these higher and / or lower concentrations are also possible, for example, the metal species can be provided in the aqueous solution at a concentration between about 0.01 M and 0.1 M. In some embodiments, the silver metal species can be provided in the aqueous solution at a concentration of at least about 0.01 M, 0.02 M, 0.03 M, 0.04 M, 0.05 M, 0.06 M, 0.07 M, 0.08 M, 0.09 M, 0.1 M, 0.2 M, 0.3 M, 0.4 M, 0.5 M, or 1.0 M. In some embodiments, the silver metal species may be provided in the aqueous solution at a concentration of less than about 1.0 M, 0.5 M, 0.4 M, 0.3 M, 0.2 M, 0.1 M, 0.09 M, 0.08 M, 0.07 M, 0.06 M, 0.05 M, 0.04 M, 0.03 M, 0.02 M, or 0.01 M. Combinations of any two or more of these higher and / or lower concentrations are also possible, for example, the silver metal species may be provided in the aqueous solution at a concentration between about 0.01 M and 0.1 M.

[0191] The aqueous solution comprising metal species can be added to the aqueous solution comprising oxide species, metal dopant species, chelating agent and plasticizer at a temperature of at least 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C. (e.g., between about 60° C. to 90° C. or 70° C. to 85° C.). The aqueous solution comprising metal species can be added to the aqueous solution comprising oxide species, metal dopant species, chelating agent and plasticizer under stirring at a rate of at least 100 rpm, 200 rpm, 300 rpm, 400 rpm or 500 rpm (e.g., between about 300 rpm to 500 rpm).

[0192] The aqueous solution including the silver metal species can be added to the aqueous solution including the cerium metal species, the metal dopant species, the chelating agent and the plasticizer at a temperature of at least 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C. (e.g., between about 60° C. to 90° C. or 70° C. to 85° C.). The aqueous solution including the silver metal species can be added to the aqueous solution including the cerium metal species, the metal dopant species, the chelating agent and the plasticizer under stirring at a rate of at least 100 rpm, 200 rpm, 300 rpm, 400 rpm or 500 rpm (e.g., between about 300 rpm to 500 rpm).

[0193] Heating the gel to obtain hybrid electrode particles

[0194] At step b), the gel is heated to obtain a powder composition comprising hybrid electrode particles, i.e., an electrode composition as described herein. This heating step is essentially to thermally decompose the gel (i.e., the precursor material comprising the chelated metal species fixed in the form of a gel) to burn off and remove the organic components of the gel (e.g., pyrolysis) to obtain a powder composition comprising hybrid electrode particles.

[0195] Depending on whether the gel is aged to remove the aqueous solution prior to heating at step b), the gel may be a viscous liquid or a rigid gel. It should be understood that for the purposes of this disclosure, both physical states are still considered gels.

[0196] The gel may be heated at step b) to a suitable temperature effective to pyrolyze the organic components of the gel to obtain a powder composition consisting of hybrid electrode particles. In some embodiments, the gel is heated at a temperature of at least about 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, or 700°C in step b). The gel may be heated at a temperature of less than about 700°C, 650°C, 600°C, 550°C, 500°C, 450°C, 400°C, 350°C, or 300°C in step b). Any combination of two or more of these higher and / or lower temperatures is also possible, such as the gel being heated at a temperature between about 300°C and about 450°C in step b). In one embodiment, the gel is heated at a temperature of about 300°C, 350°C, 400°C, 450°C, or 500°C (e.g., about 450°C) in step b). Any suitable heating rate can be used, for example at least or about 100°C / hour, 120°C / hour, 140°C / hour, 150°C / hour, 170°C / hour, 180°C / hour, 200°C / hour or 250°C / hour. In some embodiments, the gel is heated in step b) for a period of at least about 10 minutes, 15 minutes, 30 minutes, 45 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 12 hours, 24 hours, 36 hours or 48 hours. In some embodiments, the gel is heated in step b) for a period of less than about 48 hours, 36 hours, 24 hours, 12 hours, 6 hours, 5 hours, 4 hours, 3 hours, 2 hours, 1 hour, 45 minutes, 30 minutes, 15 minutes or 10 minutes. The gel can be heated for a period of time within the range provided by any two of these higher and / or lower values ​​(e.g., between about 1 hour to about 24 hours, such as between about 1 hour to about 10 hours, such as between about 2 hours to about 4 hours). Combinations of any one or more of the above temperatures and times are possible, for example the gel may be heated in step b) at a temperature between about 300° C. and 600° C. and for a period of between about 2 hours and 4 hours.

[0197] Heating (e.g., pyrolysis) can be performed using a suitable furnace or hot plate. Alternatively, heating can be performed using spray pyrolysis or spray drying of the gel. It should be understood that where spray pyrolysis of the gel is desired, it is not necessary to age the gel to remove the aqueous solution prior to any pyrolysis, as the gel needs to still be flowable in order to be spray pyrolyzed / dried.

[0198] In some embodiments, the gel prepared at step a) can be deposited on a suitable substrate (eg, by spin coating, dip coating, etc.) and then subjected to heat treatment to decompose the organic components to form a powder composition layer including hybrid electrode particles on the substrate.

[0199] The powder composition may be an amorphous, semi-crystalline or crystalline powder composition. For example, the hybrid electrode particles may be amorphous, semi-crystalline or crystalline. In one embodiment, the powder composition is an amorphous powder composition comprising hybrid electrode particles.

[0200] In some embodiments, the powder composition comprising hybrid electrode particles (i.e., an electrode composition as described herein) can be further processed into a dry powder formulation or a wet coating formulation comprising one or more solvents. The wet coating formulation can be a dip coating formulation or a printable ink formulation as described herein.

[0201] Sintered powder composition or its preparation

[0202] The powder composition or its coating formulation including the hybrid electrode particles can be sintered to form a sintered electrode material as described herein. In one embodiment, sintering includes heating the powder composition or coating formulation including the hybrid electrode particles to a temperature that effectively agglomerates and causes the metal particles in the hybrid electrode particles to adhere to each other to form a continuous or semi-continuous metal phase. After sintering to form a metal phase (i.e., a scaffold including a porous silver metal phase), the metal-doped oxide particles (e.g., metal-doped cerium oxide particles) can remain in the form of discrete particles attached to the surface of the metal phase (e.g., silver), and / or can also adhere to other metal-doped oxide particles (e.g., metal-doped cerium oxide particles) to form one or more discrete metal-doped oxide phases (e.g., portions) attached to the surface of the metal phase (e.g., silver). The sintered electrode material includes a metal phase (e.g., silver) as a porous scaffold and a plurality of discrete metal-doped oxide phases (e.g., metal-doped cerium oxide particles) dispersed in the metal phase (e.g., silver).

[0203] In one embodiment, sintering is performed at a temperature (in ° C) between about 100 and about 900. In one embodiment, sintering is performed at a temperature (in ° C) of at least about 100, 200, 300, 400, 500, 700, or 900. In one embodiment, sintering is performed at a temperature (in ° C) of less than about 900, 700, 500, 400, 300, 200, or 100. The sintering temperature can be within a range provided by any two of these higher and / or lower values, for example, between about 400° C. and about 900° C.

[0204] In one embodiment, sintering is carried out at a heating rate (in ° C / hour) between about 50 and 300, between about 100 and 200, or between about 150 and 180. Sintering can be carried out at a heating rate (in ° C / hour) of at least about 50, 70, 100, 120, 150, 180, 200, 250 or 300. Sintering can be carried out at a heating rate (in ° C / hour) of less than about 300, 250, 200, 180, 150, 120, 100, 70 or 50. The sintering heating rate can be within the range provided by any two of these higher values ​​and / or lower values. Sintering can be carried out using any suitable equipment, such as a sintering furnace or a high temperature furnace or oven.

[0205] In one embodiment, the method further comprises manufacturing an electrode. For example, the powder composition or its sintered electrode material can be used to manufacture the electrode. The electrode can be used in a solid oxide electrolysis cell unit or a solid oxide fuel cell unit.

[0206] In one embodiment, the method further includes preparing a solid oxide electrochemical cell, the solid oxide electrochemical cell including an electrode, the electrode including a powder composition or its sintered electrode material. The solid oxide electrochemical cell may include a positive electrode and a negative electrode each including a powder composition or its sintered electrode material. For example, the powder composition or its sintered electrode material can be used as both a positive electrode and a negative electrode, such as a positive electrode and a negative electrode for forming a symmetrical and reversible solid oxide electrochemical cell. This allows for faster manufacture of solid oxide electrochemical cells, because both the positive electrode and the negative electrode can be heat treated (e.g., sintered) simultaneously when preparing the solid oxide electrochemical cell. The heat treatment can also be carried out at a lower temperature than the temperature of the conventional method for preparing a conventional electrode for a solid oxide electrochemical cell. The method for manufacturing a solid oxide electrochemical cell is described below.

[0207] Electrodes and solid oxide electrochemical cells

[0208] The present disclosure also provides an electrode, which includes an electrode composition or a sintered electrode material thereof, wherein the electrode composition includes the hybrid electrode particle described herein, and the electrode composition or the sintered electrode material thereof can be used as an electrode in a solid oxide electrochemical cell.

[0209] The present disclosure also provides an electrode comprising the electrode composition described herein or a sintered electrode material thereof, which can be used as an electrode in a solid oxide electrochemical cell. The general components of a solid oxide electrochemical cell are well known and well understood in the field of the present disclosure. The solid oxide electrochemical cell comprises:

[0210] Positive electrode;

[0211] Negative electrode;

[0212] a solid electrolyte in solid communication with the positive electrode and the negative electrode; and

[0213] A circuit connects the positive electrode and the negative electrode.

[0214] The positive electrode may also be referred to as an anode, and the negative electrode may also be referred to as a cathode. These electrodes function as cathodes or anodes, depending on whether the solid oxide electrochemical cell is operated in a regeneration mode (e.g., for a solid oxide electrolysis cell (SOEC)) or an energy generation mode (e.g., for a solid oxide fuel cell (SOFC)).

[0215] In one embodiment, the solid oxide electrochemical cell can be a solid oxide electrolysis cell (SOEC). The basic operation of the solid oxide electrolysis cell is described as follows: the input stream (e.g., CO2 and H2O) flows into the cell through the inlet and flows into the negative electrode (e.g., the fuel electrode or cathode). When a voltage is applied, the input stream (e.g., CO2 and H2O) is reduced in the negative electrode (e.g., syngas: CO and H2), and the mobile oxygen species (e.g., oxygen ions (O 2- )). The oxygen ions travel through the solid oxide electrolyte and into the positive electrode (e.g., oxygen electrode or anode) where they are oxidized to molecular oxygen (O2) and produce electrons (e - ). These electrons flow from the positive electrode (i.e., the anode) into the circuit, return to the negative electrode (i.e., the cathode), and the negative electrode uses the electrons to reduce the oxygen atoms and start the process again.

[0216] It has been found that, as described herein, SOEC can generate fuel gas directly in the feed stream without any additional reducing gas, such as H2 or CO. Using prior art / conventional materials, additional supply of reducing gas is required during startup and shutdown to prevent cathode oxidation, such as oxidation of nickel to nickel oxide, which can lead to performance degradation. Advantageously, no additional reducing gas is required to maintain the metallic properties of the hybrid electrode because the electrode composition or sintered electrode material as described herein is efficient and stable in both oxidizing and reducing environments. In addition, the hybrid electrode described herein requires less electrical energy per unit volume of hydrogen or carbon monoxide or a mixture of the two (syngas) compared to conventional Ni-YSZ electrodes.

[0217] In an alternative embodiment, the solid oxide electrochemical cell may be a solid oxide fuel cell (SOFC). A SOFC is a reverse-operating SOEC that directly generates electricity by oxidizing a fuel. The basic operation of a solid oxide fuel cell is described as follows: Air flows into the cell through an inlet. As air flows over the negative electrode (e.g., the oxygen electrode or cathode), the oxygen atoms are reduced in the cathode to produce oxygen ions (O 2- ), the oxygen ions flow toward the solid oxide electrolyte. The oxygen ions travel through the solid oxide electrolyte and enter the positive electrode (e.g., the fuel electrode or anode), and then react with the fuel source (e.g., hydrogen) at the positive electrode. The reaction of the oxygen ions with the hydrogen at the positive electrode produces H2O and electrons (e - ). These electrons flow from the positive electrode (i.e., the anode) into the circuit and back into the negative electrode (i.e., the cathode). The circuit uses the electron flow to power the device, and the negative electrode uses the electrons to reduce the oxygen atoms and start the process again.

[0218] One or more advantages of the present disclosure according to at least some embodiments or examples as described herein is that the same electrode composition or its sintered electrode material can be used for both the positive electrode and the negative electrode in the solid oxide electrochemical cell unit, and the time and cost of SOEC / SOFC manufacturing, for example, are reduced. It should be understood that, in general, different materials are used to manufacture the negative electrode (e.g., nickel-YSZ composite material) and the positive electrode (e.g., LSM-YSZ composite material) of the prior art solid oxide electrolysis cell unit. Therefore, when two different materials are used, the temperature used for heat treatment during the manufacturing process is different and a two-step process is required, in which the negative electrode is typically manufactured using a heat treatment of 1500°C, followed by the positive electrode, typically manufactured at 900°C to 1100°C. In contrast, one advantage of using the same material for both the positive electrode and the negative electrode is that the electrodes can be manufactured in a single step.

[0219] Advantageously, as mentioned above, the same electrode composition or sintered electrode material thereof can be used for both the positive electrode and the negative electrode, which is one of the major limitations of existing SOE technology. In addition, it was unexpectedly found that the electrode composition or sintered electrode material thereof as described herein is not susceptible to degradation issues due to its stability in both fuel and oxidative environments, and can therefore be used in a variety of heterogeneous applications.

[0220] It should be understood that this method can also reduce the solid oxide cell operating temperature for the desired conversion rate and reduce the overall volume and cost of solid oxide cell manufacturing. In addition, due to the advantageous symmetrical cell configuration, solid oxide cell manufacturing / capital costs and time can be significantly reduced.

[0221] In some embodiments, the solid oxide electrochemical cell is a tubular solid oxide electrochemical cell. Some of the additional advantages of the present disclosure according to at least some embodiments or examples as described herein are that, compared to planar cell structures, tubular cell structures can provide increased durability, extended life, and improved performance while allowing integration with intermittent renewable energy sources. For example, in use, the tubular cell structure of the SOEC can advantageously provide improved heat dissipation (e.g., the electrolyzer can be ramped up in less than 30 minutes), and can be effectively used in transient power management schemes to convert excess electricity production into, for example, hydrogen.

[0222] In some embodiments, the electrode composition or its sintered electrode material can be used as a positive electrode and / or a negative electrode in a solid oxide electrochemical cell. In one embodiment, the electrode composition or its sintered electrode material can be used as both a positive electrode and a negative electrode of a solid oxide electrochemical cell.

[0223] Therefore, the present disclosure also provides a solid oxide electrochemical cell, which comprises a cathode, a solid oxide electrolyte and an anode, wherein the cathode and / or the anode comprises the electrode composition as described herein or the sintered electrode material as described herein.

[0224] Electrode composition

[0225] In some embodiments, the positive electrode or negative electrode comprises an electrode composition as described herein or a sintered electrode material thereof. For example, the positive electrode and the negative electrode are the same electrode material. It should be understood that such an arrangement is referred to as a symmetrical solid oxide electrochemical cell. The sintered electrode material can be produced by heating (e.g., firing) an electrode composition comprising hybrid electrode particles so that the metal particles (e.g., silver) in the hybrid electrode particles agglomerate and adhere to each other to form a continuous or semi-continuous metal phase (e.g., silver) in the electrode material.

[0226] The metal phase may include at least one metal particle selected from silver (Ag), iron (Fe), nickel (Ni) and cobalt (Co). In some embodiments, the metal phase may include a combination of silver (Ag) particles and one or more of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu) and titanium (Ti). The silver metal phase may include one or more silver metal portions. In some embodiments, the metal phase is a porous support. In some embodiments, the silver metal phase is a porous support. In some embodiments, the sintered electrode material includes a metal phase as a porous support and a plurality of discrete metal-doped oxide phases dispersed in the metal phase. The discrete metal-doped oxide phases may be in the form of metal-doped oxide particles as described herein. Discrete metal-doped oxide phases (e.g., particles or portions) may be dispersed in the metal phase. In one embodiment, the sintered electrode material includes a silver metal phase as a porous support and a plurality of discrete metal-doped cerium oxide phases dispersed in the silver metal phase. The discrete metal-doped cerium oxide phases may be in the form of metal-doped cerium oxide particles as described herein. Discrete metal-doped ceria phases (e.g., particles or portions) may be dispersed within the silver metal phase. The sintered electrode material of the cathode and / or anode may be a sintered electrode material as described herein for an electrode composition. The electrode composition or its sintered electrode material may be a coating on an electrode support.

[0227] Positive electrode

[0228] The positive electrode may also be referred to as the anode. When used in SOEC, the anode may also be referred to as the oxygen electrode. When used in SOFC, the anode may also be referred to as the fuel electrode. In some embodiments, the electrode composition or its sintered electrode material may be used as the positive electrode. Alternatively, according to some embodiments or examples, in the case of using the electrode composition or its sintered electrode material as the negative electrode, any conventional electrode material used in the solid oxide electrochemical cell may be used as the positive electrode. The positive electrode may be porous to provide a uniform flow of oxygen throughout the electrode. The positive electrode may also be a porous electrode capable of transferring oxide ions (O 2- ) is any suitable material that conducts to the solid oxide electrolyte.

[0229] In some embodiments, in the case where the negative electrode comprises an electrode composition or a sintered electrode material thereof, the positive electrode may be selected from lanthanum strontium manganate (LSM), lanthanum strontium cobalt ferrite (LSCF), strontium samarium cobalt oxide (SSC), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSCO), barium strontium cobalt iron oxide (BSCF) or a combination thereof, and also a composite thereof with yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (SSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), samarium-neodymium oxide-doped ceria (SNDC), erbium oxide-stabilized bismuth oxide (ESB), yttria-stabilized bismuth oxide (YSB), strontium and magnesium-doped lanthanum gallate (LSGM). In one embodiment, the positive electrode comprises an electrode composition as described herein or a sintered electrode material thereof.

[0230] Negative electrode

[0231] The negative electrode may also be referred to as a cathode. When used in SOEC, the cathode may also be referred to as a fuel electrode. When used in SOFC, the cathode may also be referred to as an oxygen electrode. In some embodiments, an electrode composition or a sintered electrode material thereof may be used as a negative electrode. Alternatively, according to some embodiments or examples, in the case of using an electrode composition or a sintered electrode material as a positive electrode, any conventional electrode material used in a solid oxide electrochemical cell may be used as a negative electrode. The negative electrode may be a porous layer that allows fuel gas / reactant gas to flow through the entire electrode, and in some embodiments, is conductive both electrically and ionically.

[0232] In some embodiments, in the case where the positive electrode comprises an electrode composition or a sintered electrode material thereof, the negative electrode may comprise a combination of ceramic and metal (cermet) prepared by standard ceramic processing techniques. Non-limiting examples of cermets that may be used as negative electrodes include nickel-yttria-stabilized zirconia (Ni-YSZ), nickel-gadolinium-doped ceria (Ni-GDC), nickel-yttria-doped ceria zirconia (Ni-YDCZ), and copper-ceria-yttria-doped zirconia (Cu-CeO2-YSZ). Other suitable negative electrode materials include lanthanum strontium manganese chromium oxide (LSCM), lanthanum strontium ferrite (LSF), lanthanum strontium titanate (LST), and vanadate (LSV). In one embodiment, the negative electrode comprises an electrode composition as described herein or a sintered electrode material thereof.

[0233] Solid Oxide Electrolyte

[0234] The solid oxide electrolyte may be selected from any conventionally known electrolyte capable of diffusing oxygen ions between the cathode and the anode of a solid oxide electrochemical cell. Examples of suitable solid oxide electrolytes include, but are not limited to, yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (SSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), samarium oxide-neodymium oxide-doped ceria (SNDC), erbium oxide-stabilized bismuth oxide (ESB), yttria-stabilized bismuth oxide (YSB), strontium and magnesium-doped lanthanum gallate (LSGM), and combinations thereof. In one embodiment, the solid oxide electrolyte is yttria-stabilized zirconia (YSZ). The solid oxide electrolyte may also be provided in the form of one or more layers, wherein each layer may be independently selected from the solid oxide electrolytes described above.

[0235] Additional components

[0236] The solid oxide electrochemical cell may include one or more additional components. This may include a current collector (such as silver paste, platinum paste, silver mesh, silver wire and platinum mesh), a power source and / or an interconnect. It should be understood that other additional components may be present as understood by those skilled in the art.

[0237] application

[0238] In one embodiment, the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC) configured to synthesize one or more of oxygen, hydrogen, carbon monoxide, or syngas.

[0239] In one embodiment, the solid oxide electrochemical cell unit is a solid oxide fuel cell unit (SOFC), which is used to convert chemical energy from one or more of hydrogen, ammonia, hydrocarbons (e.g., methane), natural gas, alcohols (e.g., methanol or ethanol), synthesis gas, solid carbon and biomass SOFC into electrical energy and / or thermal energy.

[0240] The present disclosure also provides a use of the electrode composition as described herein or a sintered electrode material thereof in preparing an electrode or an electrode material of a solid oxide electrochemical cell as described herein.

[0241] In some embodiments, the electrode polarization resistance of an electrode comprising an electrode composition as described herein or a sintered electrode material thereof or a solid oxide electrochemical cell as described herein can be low. In some embodiments, the electrode polarization resistance (Ohms-cm at an applied potential of 1.2 volts) is 2 ) can be less than about 0.5, 0.4, 0.3, 0.2, 0.1, 0.05, or 0.01. Electrode polarization resistance (Ohms-cm at an applied potential of 1.2 volts)2 ) can be greater than about 0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5. Combinations of these values ​​are also possible, such as between about 0.01 to 0.5, 0.05 to 0.4, or 0.1 to 0.3. The electrode polarization resistance can be less than about 0.2. The electrode polarization resistance can be measured using ASTM G59-97.

[0242] In some embodiments, electrodes comprising an electrode composition as described herein or a sintered electrode material thereof facilitate steam and / or carbon dioxide electrolysis to produce hydrogen and / or carbon monoxide, for example when used as a positive electrode and a negative electrode in a symmetrical battery cell. In other embodiments, electrodes comprising an electrode composition as described herein or a sintered electrode material thereof can be applied to ammonia synthesis and one-step methane synthesis based on solid oxide electrolysis.

[0243] According to at least some examples or embodiments described herein, electrochemical cells (eg, solid oxide electrochemical cells) fabricated using electrodes including an electrode composition as described herein or a sintered electrode material thereof may exhibit enhanced performance and / or improved stability.

[0244] In some embodiments, an electrochemical cell fabricated using an electrode comprising an electrode composition as described herein or a sintered electrode material thereof can maintain performance over at least 100, 200, 300, 400, or 500 redox cycles, thereby exhibiting enhanced performance and / or improved stability of the electrochemical cell.

[0245] In some embodiments, the performance of an electrochemical cell made using an electrode including hybrid electrode particles as described herein can be at least 5%, 10%, 15%, 20%, 25%, 30%, 35%, or 40% higher than the performance of an electrochemical cell made using an electrode made by mixing discrete cerium oxide particles with metallic silver particles. Combinations of these values ​​may also result in a range of higher performance, for example, between 5% and 40%.

[0246] In some embodiments, the electrode polarization resistance of an electrochemical cell manufactured using an electrode comprising hybrid electrode particles as described herein can be at least 5%, 10%, 15%, 20%, 25%, 30%, 35%, or 40% lower than the electrode polarization resistance of an electrochemical cell manufactured using an electrode manufactured by mixing discrete cerium oxide particles with metallic silver particles. Combinations of these values ​​may also form a range of lower electrode polarization resistances, such as between 25% and 40%. Lower electrode polarization provides improved kinetics and performance.

[0247] Method for manufacturing an electrochemical battery cell

[0248] The present disclosure also provides a method of making an electrochemical cell comprising at least one electrode comprising an electrode composition comprising the hybrid electrode particles described herein or a sintered electrode material described herein.

[0249] In one embodiment, a method of making a solid oxide electrochemical cell is provided, the method comprising:

[0250] a) preparing one or more solid oxide electrolyte layers;

[0251] b) applying an electrode composition to one or both sides of the solid oxide electrolyte layer to form a solid oxide electrochemical cell assembly, wherein the electrode composition applied to at least one side of the solid oxide electrolyte layer comprises an electrode composition as described herein; and

[0252] c) sintering the electrode composition applied to the solid oxide electrochemical cell assembly to form an electrode or electrode material.

[0253] In one embodiment, step b) includes applying the electrode composition to both sides of the solid oxide electrolyte layer. Any suitable process can be used to apply the electrode composition to the solid oxide electrolyte layer, such as by dip coating the solid oxide electrolyte layer into a wet coating formulation comprising the electrode composition to coat both sides of the layer with the electrode composition for forming the positive electrode and the negative electrode on the solid oxide electrolyte layer.

[0254] Sintering of the solid oxide electrochemical cell assembly including the electrode composition can be performed as described herein in connection with sintering of the electrode composition.

[0255] In another embodiment, a method of making a solid oxide electrochemical cell is provided, the method comprising:

[0256] a) preparing one or more solid oxide electrolyte layers;

[0257] b) applying a sintered electrode material to one or both sides of the solid oxide electrolyte layer to form a solid oxide electrochemical cell assembly, wherein the sintered electrode material applied to at least one side of the solid oxide electrolyte layer comprises a sintered electrode material described herein.

[0258] In one embodiment, the solid oxide electrochemical cell is a symmetrical cell comprising a positive electrode and a negative electrode on opposite sides of the solid oxide electrolyte layer, each electrode comprising or consisting of an electrode composition described herein or a sintered electrode material thereof.

[0259] Any one of the following numbered paragraphs or any combination of these paragraphs may provide additional embodiments of the present disclosure:

[0260] 1. An electrode composition comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises a silver particle having a surface comprising one or more metal-doped ceria particles.

[0261] 2. The electrode composition according to any one or more embodiments described herein, wherein the one or more metal-doped ceria particles are decorated on the surface of the silver particles.

[0262] 3. The electrode composition according to any one or more embodiments described herein, wherein the particle size of the silver particles is larger than the particle size of the metal-doped ceria particles.

[0263] 4. The electrode composition according to any one or more embodiments described herein, wherein the particle size (in μm) of the hybrid electrode particles is between about 0.1 and 5.

[0264] 5. The electrode composition according to any one or more embodiments described herein, wherein the particle size (in μm) of the silver particles of each hybrid electrode particle is between about 0.1 and 3.

[0265] 6. The electrode composition according to any one or more embodiments described herein, wherein the particle size (in nm) of the metal-doped ceria particles on the surface of the silver particles is between about 1 and 200.

[0266] 7. The electrode composition according to any one or more embodiments described herein, wherein the metal dopant of the ceria particles is provided by one or more metals selected from rare earth metals and alkaline earth metals.

[0267] 8. An electrode composition according to any one or more embodiments described herein, wherein the metal dopant of the cerium dioxide particles is provided by one or more metals selected from the group consisting of samarium (Sm), gadolinium (Gd), lanthanum (La), zirconium (Zr), yttrium (Y), ytterbium (Yb), erbium (Er), praseodymium (Pr) or neodymium (Nd).

[0268] 9. The electrode composition according to any one or more embodiments described herein, wherein the metal dopant of the ceria particles is provided by one or more metals selected from the group consisting of gadolinium (Gd), samarium (Sm) and yttrium (Y).

[0269] 10. The electrode composition according to any one or more embodiments described herein, wherein the amount of the metal dopant in the cerium oxide particles (based on the total weight of the metal-doped cerium oxide particles, w / w %) is between about 1 and 35.

[0270] 11. The electrode composition according to any one or more embodiments described herein, wherein the metal-doped cerium oxide particles have the formula Ce 1-x M x O 2-δ , wherein x is between about 0.01 and 0.3, M is one or more dopants defined above, and δ is between about 0.0 and 0.5.

[0271] 12. The electrode composition according to any one or more embodiments described herein, wherein the composition is provided in the form of a coating formulation comprising the hybrid electrode particles in powder form in one or more solvents.

[0272] 13. The electrode composition according to any one or more embodiments described herein, wherein the coating formulation is a dip coating formulation comprising the powder, one or more organic solvents, and optionally one or more binders.

[0273] 14. The electrode composition according to any one or more embodiments described herein, wherein the coating formulation is a printable ink formulation comprising the powder, one or more organic solvents, and optionally one or more binders.

[0274] 15. The electrode composition according to any one or more embodiments described herein, wherein the electrode composition is provided in the form of a sintered electrode material.

[0275] 16. The electrode composition according to any one or more embodiments described herein, wherein the sintered electrode material comprises a silver metal phase as a porous scaffold and a plurality of discrete metal-doped ceria phases dispersed within the silver metal phase.

[0276] 17. The electrode composition according to any one or more embodiments described herein, wherein the discrete metal-doped cerium oxide phases are in the form of metal-doped cerium oxide particles.

[0277] 18. The electrode composition according to any one or more embodiments described herein, wherein the sintered electrode material comprises 3 The silver metal phase contains between about 10 and 100 discrete metal-doped ceria phases.

[0278] 19. The electrode composition according to any one or more embodiments described herein, wherein the porosity (in volume %) of the sintered electrode material is between about 10 and 60 based on the total volume of the sintered electrode material.

[0279] 20. The electrode composition according to any one or more embodiments described herein, wherein the thickness (in μm) of the sintered electrode material is between 1 and 100.

[0280] 21. An improved sol-gel process for preparing hybrid electrode particles, wherein the process comprises:

[0281] a) preparing a gel from an aqueous solution comprising a silver metal species, a cerium metal species, a metal dopant species, a plasticizer, and a chelating agent; and

[0282] b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

[0283] 22. The improved sol-gel method according to any one or more embodiments described herein, wherein step a) comprises preparing an aqueous solution comprising the cerium metal species and the metal dopant species, followed by adding the chelating agent, the plasticizer to the aqueous solution, and then adding the silver metal species to the aqueous solution.

[0284] 23. The improved sol-gel process according to any one or more embodiments described herein, wherein the aqueous solution comprising the cerium metal species, the metal dopant species, the chelating agent and the plasticizer is aged prior to adding the silver metal species.

[0285] 24. The improved sol-gel process according to any one or more embodiments described herein, wherein after step a) but before step b), the process comprises aging the gel for a certain period of time and at a suitable temperature to any residual aqueous solution prior to the heating at step b).

[0286] 25. The improved sol-gel process according to any one or more embodiments described herein, wherein the aqueous solution and / or the gel is aged over a period of time between about 12 hours and 36 hours and at a temperature between about 60°C and 90°C.

[0287] 26. The improved sol-gel method according to any one or more embodiments described herein, wherein one or more of the cerium metal species, the metal dopant species and the silver metal species are provided in the form of a salt or a hydrate thereof, and the salt or the hydrate thereof is independently selected from hydroxides, chlorides, nitrates and oxide salts.

[0288] 27. The improved sol-gel process according to any one or more embodiments described herein, wherein one or more of the cerium metal species, the metal dopant species and the silver metal species are provided in the form of nitrates or hydrates thereof.

[0289] 28. The improved sol-gel process according to any one or more embodiments described herein, wherein the cerium metal species and the metal dopant species are each provided in the aqueous solution at a concentration between about 0.01 M and 0.1 M.

[0290] 29. The improved sol-gel process according to any one or more embodiments described herein, wherein the silver metal species is provided in the aqueous solution at a concentration between about 0.01 M and 0.1 M.

[0291] 30. The improved sol-gel process according to any one or more embodiments described herein, wherein the molar ratio of silver metal species to cerium metal species is about 1:5 to 5:1.

[0292] 31. The improved sol-gel process according to any one or more embodiments described herein, wherein the molar ratio of the metal dopant species to the cerium metal species is about 1:50 to 1:1.

[0293] 32. The improved sol-gel process according to any one or more embodiments described herein, wherein the plasticizer is a glycol, preferably selected from ethylene glycol, diethylene glycol and triethylene glycol.

[0294] 33. The improved sol-gel method according to any one or more embodiments described herein, wherein the chelating agent is selected from carboxylic acids (e.g., citric acid), amines, amino acids, amino polycarboxylic acids (e.g., EDTA), diesters, β-diketones, β-ketoesters, and any combination thereof.

[0295] 34. The improved sol-gel process according to any one or more embodiments described herein, wherein the molar ratio of the chelating agent to the silver metal species is between about 1:5 and 5:1.

[0296] 35. The improved sol-gel process according to any one or more embodiments described herein, wherein in step b) the gel is heated at a temperature between about 300°C and 600°C.

[0297] 36. The improved sol-gel method according to any one or more embodiments described herein, wherein step b) comprises flame spray pyrolysis or spray drying of the gel obtained from step a) to obtain the powder composition consisting of hybrid electrode particles.

[0298] 37. The improved sol-gel process according to any one or more embodiments described herein, wherein the powder composition comprising the hybrid electrode particles is further processed into a dry powder formulation or a wet coating formulation comprising one or more solvents.

[0299] 38. The improved sol-gel process according to any one or more embodiments described herein, wherein the coating formulation is a dip coating formulation comprising one or more solvents.

[0300] 39. The improved sol-gel process according to any one or more embodiments described herein, wherein the coating formulation is a printable ink formulation comprising a powder, one or more organic solvents and one or more stabilizers.

[0301] 40. The improved sol-gel process according to any one or more embodiments described herein, wherein the powder composition or formulation thereof is sintered into a sintered electrode material.

[0302] 41. The improved sol-gel process according to any one or more embodiments described herein, wherein the sintering is performed at a temperature between about 500°C and 900°C.

[0303] 42. The improved sol-gel method according to any one or more embodiments described herein, wherein the sintered electrode material comprises a silver metal phase as a porous scaffold and a plurality of discrete metal-doped cerium dioxide phases dispersed within the silver metal phase.

[0304] 43. The improved sol-gel method according to any one or more embodiments described herein, wherein an electrode is manufactured using the powder composition or a sintered electrode material thereof.

[0305] 44. The improved sol-gel process according to any one or more embodiments described herein, wherein a solid oxide electrochemical cell comprising an electrode comprising the powder composition or a sintered electrode material thereof is prepared.

[0306] 45. The improved sol-gel process according to any one or more embodiments described herein, wherein the solid oxide electrochemical cell comprises a positive electrode and a negative electrode each comprising the powder composition or a sintered electrode material thereof.

[0307] 46. ​​An electrode comprising the electrode composition according to any one or more embodiments described herein or a sintered electrode material thereof.

[0308] 47. A solid oxide electrochemical cell comprising a cathode, a solid oxide electrolyte and an anode, wherein the cathode and / or the anode comprises an electrode composition according to any one or more embodiments described herein or a sintered electrode material thereof.

[0309] 48. An electrode or solid oxide electrochemical cell according to any one or more embodiments described herein, wherein the sintered electrode material of the electrode composition comprises a silver metal phase as a porous support and a plurality of discrete metal-doped cerium dioxide phases dispersed within the silver metal phase.

[0310] 49. The electrode or solid oxide electrochemical cell according to any one or more of the embodiments described herein, wherein the discrete metal-doped cerium oxide phases are in the form of metal-doped cerium oxide particles.

[0311] 50. The electrode or solid oxide electrochemical cell according to any one or more embodiments described herein, wherein the particle size (in nm) of the metal-doped cerium oxide particles is between about 1 and 200.

[0312] 51. The electrode or solid oxide electrochemical cell according to any one or more embodiments described herein, wherein the electrode composition or sintered electrode material thereof is coated on an electrode support.

[0313] 52. An electrode or solid oxide electrochemical cell according to any one or more embodiments described herein, wherein the porosity (in volume %) of the sintered electrode material is between about 10 and 60 based on the total volume of the sintered electrode material.

[0314] 53. The electrode or solid oxide electrochemical cell according to any one or more embodiments described herein, wherein the sintered electrode material comprises 3 The silver metal phase contains between about 50 and 500 discrete metal-doped ceria phases.

[0315] 54. A solid oxide electrochemical cell according to any one or more embodiments described herein, wherein the solid oxide electrolyte is selected from yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (SSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), samarium-neodymium oxide-doped ceria (SNDC), erbium oxide-stabilized bismuth oxide (ESB), yttria-stabilized bismuth oxide (YSB), strontium or magnesium-doped lanthanum gallate (LSGM), and combinations thereof.

[0316] 55. A solid oxide electrochemical cell according to any one or more of the embodiments described herein, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC), a solid oxide fuel cell (SOFC), or a reversible solid oxide electrochemical cell.

[0317] 56. A solid oxide electrochemical cell according to any one or more of the embodiments described herein, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC), and the SOEC is configured to synthesize one or more of oxygen, hydrogen, carbon monoxide or synthesis gas.

[0318] 57. A solid oxide electrochemical cell unit according to any one or more embodiments described herein, wherein the solid oxide electrochemical cell unit is a solid oxide fuel cell unit (SOFC), and the SOFC is used to convert chemical energy from one or more of hydrogen, ammonia, hydrocarbons, alcohols, synthesis gas, solid carbon and biomass SOFC into electrical energy and / or thermal energy.

[0319] 58. A solid oxide electrochemical cell according to any one or more of the embodiments described herein, wherein the solid oxide electrochemical cell is a symmetrical solid oxide electrochemical cell having a positive electrode and a negative electrode, each electrode comprising the electrode composition or a sintered electrode material thereof.

[0320] 59. Use of the electrode composition or sintered electrode material thereof according to any one or more embodiments described herein in preparing an electrode or electrode material for a solid oxide electrochemical cell.

[0321] 60. The use according to any one or more of the embodiments described herein, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC), a solid oxide fuel cell (SOFC) or a reversible solid oxide electrochemical cell.

[0322] 61. The use according to any one or more of the embodiments described herein, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC), and the SOEC is configured to synthesize one or more of oxygen, hydrogen, carbon monoxide or synthesis gas.

[0323] 62. The use according to any one or more embodiments described herein, wherein the solid oxide electrochemical cell unit is a solid oxide fuel cell unit (SOFC), and the SOFC is selected from hydrogen, ammonia, hydrocarbons, alcohols, synthesis gas, solid carbon and biomass SOFC.

[0324] 63. The use according to any one or more embodiments described herein, wherein the solid oxide electrochemical cell is a symmetrical solid oxide electrochemical cell having a positive electrode and a negative electrode, each electrode comprising the electrode composition or a sintered electrode material thereof.

[0325] 64. A method of making a solid oxide electrochemical cell, the method comprising:

[0326] a) preparing one or more solid oxide electrolyte layers;

[0327] b) applying an electrode composition to one or both sides of the solid oxide electrolyte layer to form a solid oxide electrochemical cell assembly, wherein the electrode composition applied to at least one side of the solid oxide electrolyte layer comprises an electrode composition according to any one or more embodiments described herein; and

[0328] c) sintering the electrode composition applied to the solid oxide electrochemical cell assembly to form an electrode or electrode material.

[0329] 65. The method of claim 64, wherein step b) comprises applying the electrode composition according to any one or more of the embodiments described herein to both sides of the solid oxide electrolyte layer.

[0330] 66. A method according to any one or more embodiments described herein, wherein the solid oxide electrochemical cell is a symmetrical cell comprising a positive electrode and a negative electrode located on opposite sides of the solid oxide electrolyte layer, each electrode comprising or consisting of an electrode composition according to any one or more embodiments described herein.

[0331] Examples

[0332] The present disclosure is further described by the following examples. It should be understood that the following description is only for the purpose of describing specific embodiments and is not intended to limit the above description.

[0333] Example 1: Preparation of hybrid electrode particles

[0334] Cerium nitrate hexahydrate and gadolinium nitrate hexahydrate are dissolved in deionized water to form an aqueous solution in which the concentration of cerium nitrate and gadolinium nitrate is between 0.01M and 0.1M (e.g., 0.02M), respectively. Then, a chelating agent (e.g., citric acid or EDTA) is added to an aqueous solution having a molar ratio of citric acid to nitrate of about 1:1 to 1:5. Then, based on the species present in the aqueous solution (e.g., rich in triethylene glycol), the aqueous solution including cerium nitrate, gadolinium nitrate and a chelating agent (e.g., citric acid and EDTA) is mixed with a plasticizer (e.g., triethylene glycol) at a ratio of about 2:1 to 4:1. Then, the aqueous solution is aged at a temperature of 70°C to 85°C in a laboratory drying oven (under natural convection) for 24 hours.

[0335] Similarly, an aqueous solution of lanthanum nitrate hexahydrate (0.100 M), strontium nitrate (0.067 M), cobalt nitrate hexahydrate (0.035 M), and ferric nitrate nonahydrate (0.140 M) was prepared and mixed thoroughly using a magnetic stirrer, followed by the addition of citric acid monohydrate (chelating agent) to the solution to give a molar ratio of nitrate: citric acid of 1: 1. Next, triethylene glycol (plasticizer) was added to the solution to give a molar ratio of (nitrate + acid): triethylene glycol of 2: 1. This liquid mixture was stirred thoroughly for 15 minutes to ensure that all chemicals were dissolved, and then aged for 24 hours at a temperature of 70° C. to 85° C. in a laboratory drying oven under natural convection.

[0336] Similarly, in another example such as bimetallic metal species and mixed oxide phases, aqueous solutions of silver nitrate (0.327 M) and ferric nitrate nonahydrate (0.127 M) were mixed thoroughly and then added dropwise to an aqueous solution comprising cerium nitrate, gadolinium nitrate, a chelating agent and a plasticizer, wherein all other steps remained exactly the same.

[0337] In a separate beaker, an aqueous solution of silver nitrate at a concentration of about 0.01M to 0.1M is prepared. The silver nitrate solution is slowly (dropwise) added to the above aqueous solution including metal nitrate, chelating agent and plasticizer while stirring on an electric plate at 70°C to 85°C under constant stirring of 300rpm to 500rpm with a laboratory stirrer (e.g., Fisher Scientific). The mixed aqueous solution (which is still liquid, viscous, but can flow) is further aged in a drying oven at a temperature between 70°C to 85°C for 24 hours, cooled to room temperature, and further aged for 4 to 8 hours to form a gel.

[0338] The gel mixture was then burned on a hot pyrolytic glass surface maintained at 450° C. to burn the organic matter and obtain a powder composition including hybrid electrode particles having a desired microstructure (eg, pyrolytic).

[0339] Example 2: Preparation of Solid Oxide Electrolysis (SOEC) Tube Cell

[0340] Solid Oxide Electrolyte Tube

[0341] Ceramic 8 mol% yttria stabilized zirconia (YSZ) tubes were fabricated by cold isostatic pressing of 8YSZ powder at 170 MPa followed by sintering at 1500°C for 4 hours. The length and OD of the tube were about 340 mm and about 11 mm, respectively. The electrolyte tube thickness was measured to be about 0.45 mm.

[0342] Fuel electrode (negative electrode) coating

[0343] The ink for the fuel electrode was prepared by mixing the powder composition (ie, the electrode composition as described herein) with a terpineol-based ink vehicle (FCM materials, USA) at a ratio of 65:35 wt %. The resulting slurry was ball milled using zirconia balls for about 2 hours.

[0344] A dip coating solution was also prepared using the powder composition of the hybrid electrode particles as follows:

[0345] Table 1: Dip coating formulations

[0346] Components quantity Hybrid electrode particles (powder compositions) 39g Polyvinyl butyral 2.8g α-Terpineol 1.39g Ethanol 16.74g total About 60g

[0347] The formulation was then applied to a solid oxide electrolyte tube by dip coating or brush coating and sintered at 600°C to 850°C for 4 hours using a heating and cooling rate of 120°C / hour. The thickness of the sintered fuel electrode including the sintered hybrid electrode particles (i.e., the sintered electrode material as described herein) was measured to be about 40 μm thick with an active area of ​​25 cm 2 .

[0348] For the tube cell using prior art electrodes, the electrode ink was prepared using a similar procedure as described previously with commercially sourced Ni-YSZ powder (FCM Materials, USA). The prior art electrodes were heat treated at 1400°C for 2 hours and then cooled to 25°C according to standard state of prior art conditions. The heating and cooling rates were 3°C / min. The electrodes were about 40 μm thick with an active cell area of ​​25 cm 2 .

[0349] Oxygen electrode (positive electrode)

[0350] For both the prior art electrode and the sintered hybrid electrode, the sintered hybrid electrode was used as the air electrode. The electrode ink was prepared by mixing the so synthesized powder with a pine alcohol-based ink vehicle (FuelCell Materials Inc.) in a weight ratio of 65:35 followed by ball milling the mixture for 2 hours. The sintering profile included heating to 825°C at 3°C / min, followed by dwelling at 825°C for 2 hours, and then cooling to 25°C at 3°C / min. Each electrode was about 40 μm thick, with an active cell area of ​​25 cm 2 .

[0351] Example 3: Testing of Solid Oxide Electrolysis (SOEC) Tube Cells

[0352] All cell tests and electrochemical measurements were performed using a symmetrical tube cell manufactured in-house. The inlet gas feed (steam or a mixture of steam / CO2 or pure CO2) was fed into the fuel chamber (located inside the tube and contacting the fuel electrode (cathode)) at a constant flow rate of 30 ml / min to 50 ml / min. The oxygen electrode (anode) was exposed to the atmosphere with a chamber air flow of 50 ml / min. A schematic diagram of the setup is shown in Fig.11 middle.

[0353] The mass flow meter was calibrated using a separate certified flow meter. A single K-type thermocouple was used to monitor the temperature at the center of the cathode, which will be designated as the operating temperature thereafter. A power supply (Keithley) and a digital multimeter (HP) were used to measure the voltage on the electrodes to extract VI curves (where reported). Except for steam electrolysis, only single-point measurements were extracted at 1.2V or 1.5V (no VI curves due to experimental measurement limitations).

[0354] Example 4: Synthetic Syngas

[0355] An inlet gas feed of a mixture of steam and CO2 was fed into the fuel chamber as described in Example 3. The amount of syngas (i.e., a mixture of hydrogen and CO 1:1 vol%) produced using a SOEC tube cell including a fuel electrode made from a sintered hybrid electrode (i.e., a sintered electrode material) was significantly higher than the amount of syngas produced using a SOEC tube cell including a fuel electrode made from a prior art electrode, as provided below:

[0356]

[0357] Example 5: Steam electrolysis

[0358] An inlet gas feed of steam was fed into the fuel chamber as described in Example 3. The amount of hydrogen produced using a SOEC tube cell including a fuel electrode made from a sintered hybrid electrode (i.e., a sintered electrode material) was significantly higher than the amount of hydrogen produced using a SOEC tube cell including a fuel electrode made from a prior art electrode, as provided below:

[0359]

[0360] Example 6: Synthesis of CO

[0361] An inlet gas feed of dry CO2 was fed into the fuel chamber as described in Example 3. The amount of CO produced using a SOEC tube cell including a fuel electrode made from a sintered hybrid electrode (i.e., a sintered electrode material) was significantly higher than the amount of CO produced using a SOEC tube cell including a fuel electrode made from a prior art electrode, as provided below:

[0362]

[0363] Example 7: Comparison with electrodes comprising discrete mixtures of Ag and GDC

[0364] The performance of a symmetrical solid oxide electrolysis cell (SOEC) prepared using electrodes prepared using sintered hybrid particles (i.e., sintered electrode materials) was compared to the performance of a SOEC prepared using electrodes prepared using discrete silver and gadolinium doped ceria particles (CGO-Ag hybrid). The symmetrical SOEC was prepared using the protocol outlined in Example 2.

[0365] Figure 6 The current-voltage (VI) curve of a symmetric SOEC for steam electrolysis after 2 hours of loading at 1.5 V is shown, wherein the SOEC includes an electrode prepared using a sintered material, wherein the sintered material includes a silver metal phase and one or more metal-doped ceria particles or discrete portions dispersed within the silver metal phase; a Ni-YSZ composite material; or a mixed CGO-AG. The increase in current caused by the SOEC including an electrode made using hybrid electrode particles can be attributed to a decrease in electrode polarization resistance. Without wishing to be bound by theory, due to the unique microstructure of the hybrid electrode particles, ion and electron pathways are generated to transfer electrons and mobile oxygen species (O 2- ) are transferred to and from reactive sites located on the surface of each hybrid electrode particle, resulting in higher performance than that of a blend of discrete silver and gadolinium doped ceria particles or conventional Ni-YSZ composites, thereby enhancing performance (e.g., reducing electrode polarization resistance).

[0366] like Figure 8 and 9 Similar improvements in performance were seen in other electrode configurations such as hybrid electrode particles where the electrode included Ag and one or more doped ferrite phases and bimetallic phases with one or more metal doped ceria as shown in Figure 1. Electrode polarization resistances of these cells were measured to be <0.3 ohm cm compared to blends of discrete metals and mixed ion-conducting phases. 2 ( Fig.10 ).

[0367] Example 8: Stability of electrode composition in steam electrolysis

[0368] The performance stability of a symmetric solid oxide electrolysis cell (SOEC) prepared using electrodes comprising sintered hybrid particles during steam electrolysis was evaluated. Figure 7 It is shown that after 150 hours of steam electrolysis, the current density remains between 0.5-0.55 A / cm -2 This highlights the improved performance stability of the hybrid electrode composition.

Claims

1. An electrode composition comprising a plurality of hybrid electrode particles, wherein each hybrid electrode particle comprises at least one metal phase and one oxide phase, wherein the metal phase comprises a plurality of metal particles, and the oxide phase comprises a plurality of ion- or mixed-ion-conducting oxide particles on the surface of the metal particles, wherein the plurality of ion- or mixed-ion-conducting oxide particles are decorated on the surface of the metal particles, wherein the particle size (in nm) of the ion- or mixed-ion-conducting oxide particles on the surface of the metal particles is between about 1 and 100.

2. The electrode composition according to claim 1, wherein the metal phase comprises at least one metal particle, and the at least one metal particle is selected from silver (Ag), iron (Fe), nickel (Ni) and cobalt (Co).

3. The electrode composition according to claim 1 or claim 2, wherein the metal phase comprises a combination of silver (Ag) particles and one or more of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu) and titanium (Ti). 4 . The electrode composition according to claim 1 , wherein the metal phase comprises a combination of silver (Ag) particles and iron (Fe) particles. 5 . The electrode composition according to claim 1 , wherein the metal phase comprises silver (Ag) particles.

6. The electrode composition of any one of claims 1 to 5, wherein the oxide phase comprises ion or mixed ion conducting oxide particles selected from metal (e.g., Gd, Sm, Pr, Ni) doped ceria, metal (e.g., Cu) doped ferrites, titanium doped lanthanum strontium ferrites (e.g., LSCF, LSTF) and lanthanum strontium chromium manganese (LSCM).

7. The electrode composition according to any one of claims 1 to 6, wherein the size of the metal particles is larger than the size of the ion or mixed ion conducting oxide particles.

8. The electrode composition according to any one of claims 1 to 7, wherein the particle size (in μm) of the hybrid electrode particles is between about 0.05 and 5.

9. The electrode composition according to any one of claims 1 to 8, wherein the particle size (in μm) of the metal particles of each hybrid electrode particle is between about 0.1 and 5.

10. The electrode composition according to any one of claims 1 to 9, wherein the composition is provided in the form of a coating formulation comprising the hybrid electrode particles in powder form in one or more solvents.

11. The electrode composition of claim 10, wherein the coating formulation is a dip coating formulation comprising the powder, one or more organic solvents and optionally one or more binders.

12. An electrode composition according to claim 10 or claim 11, wherein the coating formulation is a printable ink formulation comprising the powder, one or more organic solvents and optionally one or more binders.

13. The electrode composition according to any one of claims 1 to 12, wherein the electrode composition is provided in the form of a sintered electrode material.

14. The electrode composition of claim 13, wherein the sintered electrode material comprises a metal phase as a porous scaffold and a plurality of discrete oxide phases dispersed within the metal phase.

15. The electrode composition of claim 14, wherein the discrete oxide phases are in the form of ion or mixed ion conducting oxide particles.

16. The electrode composition according to any one of claims 13 to 15, wherein the sintered electrode material comprises 3 The metallic phases range from about 10 to 100 discrete oxide phases.

17. The electrode composition of any one of claims 13 to 16, wherein the porosity (in volume %) of the sintered electrode material is between about 10 and 60 based on the total volume of the sintered electrode material.

18. The electrode composition according to any one of claims 13 to 17, wherein the thickness (in μm) of the sintered electrode material is between 1 and 100.

19. An improved sol-gel method for preparing hybrid electrode particles, wherein each hybrid electrode particle comprises at least one metal phase and one oxide phase, wherein the metal phase comprises a plurality of metal particles, and the oxide phase comprises a plurality of ion or mixed ion conducting oxide particles on the surface of the metal particles, wherein the plurality of ion or mixed ion conducting oxide particles decorate the surface of the metal particles, wherein the particle size (in nm) of the ion or mixed ion conducting oxide particles on the surface of the metal particles is between about 1 and 100, wherein the method comprises: a) preparing a gel from an aqueous solution comprising a metal species, an ion or mixed ion conducting oxide species, a plasticizer and a chelating agent; as well as b) heating the gel to obtain a powder composition comprising the hybrid electrode particles.

20. The improved sol-gel process of claim 19, wherein step a) comprises preparing an aqueous solution comprising said ionic or mixed ionic conducting oxide species, followed by adding said chelating agent, said plasticizer and then said metal species to said aqueous solution.

21. The improved sol-gel process of claim 20, wherein the aqueous solution comprising the ionic or mixed ionic conducting oxide species, the chelating agent and the plasticizer is aged prior to adding the metal species.

22. The improved sol-gel process according to any one of claims 19 to 21, wherein after step a) but before step b), the process comprises aging the gel for a period of time and at a suitable temperature to any residual aqueous solution prior to the heating at step b).

23. The improved sol-gel process of claim 22, wherein the aqueous solution and / or the gel is aged over a period of time between about 12 hours and 36 hours and at a temperature between about 60°C and 90°C.

24. The improved sol-gel process according to any one of claims 19 to 23, wherein one or more of the ion or mixed ion conducting oxide species and the metal species are provided in the form of a salt or a hydrate thereof, the salt or hydrate thereof being independently selected from hydroxides, chlorides, nitrates and oxide salts.

25. The improved sol-gel process according to any one of claims 19 to 24, wherein one or more of the ion or mixed ion conducting species and the metal species are provided in the form of a nitrate or a hydrate thereof.

26. The improved sol-gel process according to any one of claims 19 to 25, wherein the metal species comprises at least one metal particle selected from the group consisting of silver (Ag), iron (Fe), nickel (Ni) and cobalt (Co).

27. The improved sol-gel process according to any one of claims 19 to 26, wherein the metal phase comprises a combination of silver (Ag) particles and one or more of iron (Fe), nickel (Ni), cobalt (Co), copper (Cu) and titanium (Ti).

28. The improved sol-gel process according to any one of claims 19 to 27, wherein the oxide phase consists of ion or mixed ion conducting oxide particles selected from metal (e.g., Gd, Sm, Pr, Ni) doped ceria, metal (e.g., Cu) doped ferrites, titanium doped lanthanum strontium ferrites (e.g., LSCF, LSTF) and lanthanum strontium chromium manganese (LSCM).

29. The improved sol-gel process of any one of claims 19 to 28, wherein the molar ratio of metal species to ionic or mixed ionic conducting oxide species is about 1:5 to 5:

1.

30. The improved sol-gel process according to any one of claims 19 to 29, wherein the plasticizer is a glycol, preferably selected from ethylene glycol, diethylene glycol and triethylene glycol.

31. The improved sol-gel process according to any one of claims 19 to 30, wherein the chelating agent is selected from carboxylic acids (e.g., citric acid), amines, amino acids, amino polycarboxylic acids (e.g., EDTA), diesters, β-diketones, β-ketoesters, and any combination thereof.

32. The improved sol-gel process according to any one of claims 19 to 31, wherein the gel is heated at a temperature between about 300°C and 600°C in step b).

33. The improved sol-gel process according to any one of claims 19 to 32, wherein step b) comprises flame spray pyrolysis or spray drying of the gel obtained from step a) to obtain the powder composition consisting of hybrid electrode particles.

34. The improved sol-gel process according to any one of claims 19 to 33, wherein the powder composition comprising the hybrid electrode particles is further processed into a dry powder formulation or a wet coating formulation comprising one or more solvents.

35. The improved sol-gel process of claim 34, wherein the coating formulation is a dip coating formulation comprising one or more solvents.

36. The improved sol-gel process of claim 35, wherein the coating formulation is a printable ink formulation comprising a powder, one or more organic solvents and one or more stabilizers.

37. The improved sol-gel process according to any one of claims 19 to 36, wherein the powder composition or formulation thereof is sintered into a sintered electrode material.

38. The improved sol-gel process of claim 37, wherein the sintering is performed at a temperature between about 500°C and 900°C.

39. The improved sol-gel process of claim 37 or claim 38, wherein the sintered electrode material comprises a metal phase as a porous scaffold and a plurality of discrete ion or mixed ion conducting oxide phases dispersed within the metal phase.

40. The improved sol-gel process according to any one of claims 19 to 39, wherein an electrode is manufactured using the powder composition or a sintered electrode material thereof.

41. The improved sol-gel process according to any one of claims 19 to 40, wherein a solid oxide electrochemical cell is prepared comprising an electrode comprising the powder composition or a sintered electrode material thereof.

42. The improved sol-gel process of claim 41, wherein the solid oxide electrochemical cell comprises a positive electrode and a negative electrode each comprising the powder composition or a sintered electrode material thereof.

43. An electrode comprising the electrode composition according to any one of claims 1 to 18 or a sintered electrode material thereof.

44. A solid oxide electrochemical cell comprising a cathode, a solid oxide electrolyte and an anode, wherein the cathode and / or the anode comprises the electrode composition according to any one of claims 1 to 18 or a sintered electrode material thereof.

45. An electrode or solid oxide electrochemical cell according to claim 43 or claim 44, wherein the sintered electrode material of the electrode composition comprises a metal phase as a porous scaffold and a plurality of discrete ion or mixed ion conducting oxide phases dispersed within the silver metal phase.

46. ​​An electrode or solid oxide electrochemical cell according to any one of claims 43 to 45, wherein the electrode composition or sintered electrode material thereof is coated on an electrode support.

47. An electrode or solid oxide electrochemical cell according to any one of claims 43 to 45, wherein the porosity (in volume %) of the sintered electrode material is between about 10 and 60 based on the total volume of the sintered electrode material.

48. An electrode or solid oxide electrochemical cell according to any one of claims 43 to 46, wherein the sintered electrode material comprises 3 The metallic phases are between about 50 and 500 discrete ion or mixed ion conducting oxide phases.

49. A solid oxide electrochemical cell according to any one of claims 44 to 47, wherein the solid oxide electrolyte is selected from yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (SSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), samarium-neodymium oxide-doped ceria (SNDC), erbium oxide-stabilized bismuth oxide (ESB), yttria-stabilized bismuth oxide (YSB), strontium or magnesium-doped lanthanum gallate (LSGM), and combinations thereof.

50. The solid oxide electrochemical cell of any one of claims 44 to 48, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC), a solid oxide fuel cell (SOFC), or a reversible solid oxide electrochemical cell.

51. The solid oxide electrochemical cell of claim 49, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC) configured to synthesize one or more of oxygen, hydrogen, carbon monoxide, or syngas.

52. A solid oxide electrochemical cell unit according to claim 49, wherein the solid oxide electrochemical cell unit is a solid oxide fuel cell unit (SOFC), which is used to convert chemical energy from one or more of hydrogen, ammonia, hydrocarbons, alcohols, synthesis gas, solid carbon and biomass SOFC into electrical energy and / or thermal energy.

53. The solid oxide electrochemical cell of any one of claims 44 to 51, wherein the solid oxide electrochemical cell is a symmetrical solid oxide electrochemical cell having a positive electrode and a negative electrode, each electrode comprising the electrode composition or a sintered electrode material thereof.

54. Use of the electrode composition according to any one of claims 1 to 18 or a sintered electrode material thereof in the preparation of an electrode or electrode material for a solid oxide electrochemical cell.

55. The use according to claim 53, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC), a solid oxide fuel cell (SOFC) or a reversible solid oxide electrochemical cell.

56. The use according to claim 54, wherein the solid oxide electrochemical cell is a solid oxide electrolysis cell (SOEC), the SOEC being configured for synthesizing one or more of oxygen, hydrogen, carbon monoxide or synthesis gas.

57. Use according to claim 54, wherein the solid oxide electrochemical cell is a solid oxide fuel cell (SOFC) selected from the group consisting of hydrogen, ammonia, hydrocarbons, alcohols, synthesis gas, solid carbon and biomass SOFC.

58. The use according to any one of claims 53 to 56, wherein the solid oxide electrochemical cell is a symmetrical solid oxide electrochemical cell having a positive electrode and a negative electrode, each electrode comprising the electrode composition or a sintered electrode material thereof.

59. A method of making a solid oxide electrochemical cell, the method comprising: a) preparing one or more solid oxide electrolyte layers; b) applying an electrode composition to one or both sides of the solid oxide electrolyte layer to form a solid oxide electrochemical cell assembly, wherein the electrode composition applied to at least one side of the solid oxide electrolyte layer comprises an electrode composition according to any one of claims 1 to 18; and c) sintering the electrode composition applied to the solid oxide electrochemical cell assembly to form an electrode or electrode material.

60. The method of claim 58, wherein step b) comprises applying the electrode composition of any one of claims 1 to 18 to both sides of the solid oxide electrolyte layer.

61. A method according to claim 58 or claim 59, wherein the solid oxide electrochemical cell is a symmetrical cell comprising a positive electrode and a negative electrode located on opposite sides of the solid oxide electrolyte layer, each electrode comprising or consisting of an electrode composition according to any one of claims 1 to 18.